Compound, polymerizable composition, polymer, holographic recording medium, optical material, and optical component
A pentaerythritol compound with three aromatic rings linked to a polymerizable group addresses the need for high refractive index and polymerizability, enhancing optical materials and components with improved performance.
Patent Information
- Application Number
- CN202080075618.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-11-19
- Filing Date
- 2020-11-16
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2040-11-16
AI Technical Summary
Existing optical materials and compounds do not achieve a high enough refractive index and sufficient polymerizability for applications requiring ultra-high refractive index, particularly in holographic recording media and optical components.
A pentaerythritol compound with three aromatic rings linked to a polymerizable group via a specific linking group, forming a compound with a high refractive index and easy polymerizability, which is used in a polymerizable composition and polymer.
The compound achieves high refractive index and easy polymerizability, resulting in optical materials and components with high diffraction efficiency, high light transmittance, and low shrinkage.
Smart Images

Figure CN114616228B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a compound having a high refractive index and excellent polymerizability, and a polymerizable composition containing the compound. In addition, the present invention relates to a holographic recording medium, an optical material, and an optical component using the polymerizable composition or a polymer thereof. Background Art
[0002] In the past, glass was often used in optical components. For example, for optical lenses, even if they have the same focal length, if they are made of materials with a high refractive index, the lenses can be made thinner, which has the advantages of being lightweight and increasing the freedom of optical path design. High refractive index optical lenses are also effective for miniaturization, high resolution, and wide angle of optical imaging devices.
[0003] In recent years, highly transparent plastics have attracted attention as optical materials to replace glass. Compared with glass, plastic materials have the advantages of easy weight reduction, easy improvement of mechanical strength, and easy processing and molding. With the development of peripheral technologies, the demand for improved performance of plastic optical materials is also increasing. For example, in materials used in optical lenses, it is required to be easy to polymerize (easy polymerizability), have good curing properties, and have a high refractive index (high refractive index) of the polymer.
[0004] So far, a variety of resins have been developed for the purpose of increasing the refractive index. For example, o-phenylphenol EO-modified acrylate (Patent Document 1), 9,9-bis[4-(2-acryloyloxyethoxy)phenyl]fluorene (Patent Document 2), etc. In addition, various compounds with modified molecular structures of these compounds have been developed as homopolymers and copolymers, and research has been conducted to increase the refractive index (Patent Documents 3 and 4).
[0005] 9,9-bis[4-(2-acryloyloxyethoxy)phenyl]fluorene is frequently used as a high-refractive-index acrylate, but its viscosity is relatively high and the refractive index of the monomer is about 1.62, which is not high enough (Patent Document 5).
[0006] In order to increase the refractive index, in addition to introducing an aromatic ring, it is also effective to introduce a sulfur atom into the molecule. For example, Patent Document 6 describes a diacrylate monomer having a pentaerythritol skeleton with 1 to 2 naphthylthio groups in one molecule, and the refractive index thereof is 1.62 to 1.65.
[0007] Patent Document 7 describes an acrylate compound having a glycerol skeleton with two benzothiazole rings in one molecule, and the refractive index thereof is 1.63.
[0008] None of these substances can be said to be sufficient for applications requiring an ultra-high refractive index exceeding 1.65.
[0009] On the other hand, in order to further increase the capacity and density of optical recording media, a holographic optical recording medium has been developed, which records information in the form of a hologram by changing the refractive index of the recording layer according to the light intensity distribution caused by light interference. In addition, in recent years, research has been conducted on the application of holographic recording media developed for storage purposes to the optical element use of AR glasses light guide plates.
[0010] Patent Document 8 describes a pentaerythritol-type (meth)acrylate compound having three aromatic rings as an ultra-high refractive index compound for an optical material used in a holographic recording medium, wherein there is a description that a structure is formed in which a (meth)acryloyl group is directly bonded to a pentaerythritol skeleton in order to obtain a high refractive index. However, in this structure, sufficient polymerization performance cannot be obtained due to steric hindrance around the (meth)acryloyl group, and the holographic recording characteristics may be reduced.
[0011] Patent Document 1: Japanese Patent Application Publication No. 2013-95833
[0012] Patent Document 2: Japanese Patent Application Publication No. 2000-7741
[0013] Patent Document 3: Japanese Patent Application Publication No. 2008-94987
[0014] Patent Document 4: Japanese Patent Application Publication No. 2012-82387
[0015] Patent Document 5: Japanese Patent Application Laid-Open No. 6-220131
[0016] Patent Document 6: Japanese Patent Application No. 2008-527413
[0017] Patent Document 7: Japanese Patent Application Publication No. 2005-133071
[0018] Patent Document 8: Japanese Patent Application Publication No. 2017-14213 Summary of the invention
[0019] An object of the present invention is to provide a high refractive index compound which is useful as an optical material or an optical component and has easy polymerizability.
[0020] Means for solving technical problems
[0021] The present inventors have discovered that a pentaerythritol compound having three aromatic rings linked to a polymerizable group via a specific linking group is an easily polymerizable high refractive index compound, and that a polymerizable composition and a polymer using the compound have a high refractive index, thereby achieving the present invention.
[0022] The gist of the present invention lies in the following aspects.
[0023] [1] A compound represented by the following formula (1).
[0024] [Chemistry 1]
[0025]
[0026] [Where R 1 represents a hydrogen atom or a methyl group. 2 represents an aromatic ring group which may have a substituent, or an alkyl group substituted by an aromatic ring group which may have a substituent. 1 represents a (thio)ester bond, a (thio)carbonate bond, a (thio)amide bond, a (thio)urethane bond, a (thio)urea bond, or a (thio)ether bond, or oxygen, sulfur, or a nitrogen atom which may have a substituent. X 2 represents oxygen, sulfur or a nitrogen atom which may have a substituent. A represents a divalent group which may have a substituent. L represents an (m+1)-valent linking group which may have a substituent. m represents an integer of 1 to 3. n represents 0 or 1.]
[0027] [2] The compound as described in [1], wherein the above n is 0.
[0028] [3] The compound according to [1] or [2], wherein L is an optionally substituted hydrocarbon group having 1 to 8 carbon atoms.
[0029] [4] The compound according to [3], wherein L is an optionally substituted aliphatic hydrocarbon group having 1 to 8 carbon atoms.
[0030] [5] The compound according to [4], wherein L is an optionally substituted chain aliphatic hydrocarbon group having 1 to 8 carbon atoms.
[0031] [6] The compound according to any one of [1] to [5], wherein R 2 It is a fused aromatic heterocyclic group which may have a substituent, or an aromatic hydrocarbon group which has a fused heterocyclic ring as a substituent.
[0032] [7] The compound as described in [6], wherein the above R 2 It is a sulfur-containing condensed aromatic heterocyclic group, or an aromatic hydrocarbon group having a sulfur-containing condensed heterocyclic group as a substituent.
[0033] [8] The compound as described in [7], wherein the above R 2 It is any one of a dibenzothiophenyl group, a benzothiazolyl group and a thianthrenyl group, or it is an aromatic hydrocarbon group having any one of a dibenzothiophenyl group, a benzothiazolyl group and a thianthrenyl group as a substituent.
[0034] [9] A polymerizable composition comprising the compound according to any one of [1] to [8] and a polymerization initiator.
[0035]
[10] A holographic recording medium comprising the polymerizable composition described in [9].
[0036]
[11] A polymer obtained by polymerizing the polymerizable composition described in [9].
[0037]
[12] An optical material comprising the polymer described in
[11] .
[0038]
[13] An optical component comprising the polymer described in
[11] .
[0039]
[14] A mass storage device comprising the holographic recording medium described in
[10] .
[0040]
[15] An optical element obtained by performing holographic recording on the holographic recording medium described in
[10] .
[0041]
[16] An AR glasses comprising the optical element described in
[15] .
[0042] Effects of the Invention
[0043] According to the present invention, there is provided an easily polymerizable high refractive index compound useful as an optical material, and the compound is particularly useful as a reactive compound used in a hard coat layer of an optical lens or optical component, or a holographic recording medium.
[0044] By using the compound of the present invention, it is possible to realize an optical material or optical component having high diffraction efficiency, high light transmittance, and low shrinkage. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] Figure 1 It is a schematic diagram showing an outline of the configuration of an apparatus used for holographic recording. DETAILED DESCRIPTION
[0046] The following is a detailed description of the embodiments of the present invention. The present invention is not limited to the following embodiments, and can be implemented with various modifications within the scope of the gist.
[0047] In the present invention, "(thio)ester bond" is a general term for ester bond and thioester bond. "(thio)carbonate bond" is a general term for carbonate bond and thiocarbonate bond. "(thio)amide bond" is a general term for amide bond and thioamide bond. "(thio)carbamate bond" is a general term for carbamate bond and thiocarbamate bond. "(thio)urea bond" is a general term for urea bond and thiourea bond. "(thio)ether bond" is a general term for ether bond and thioether bond.
[0048] In the present invention, "(meth)acrylate" is a general term for acrylate and methacrylate. "(meth)acryloyl" is a general term for acryloyl and methacryloyl. "(Meth)acrylic acid" is a general term for acrylic acid and methacrylic acid.
[0049] In the present invention, "having or not having a substituent" means having one or more substituents or having no substituent.
[0050] 1. About the compounds of the present invention
[0051] The compound of the present invention is a compound represented by the following formula (1) and having a (meth)acryloyl group as a polymerizable functional group.
[0052] [Chemistry 2]
[0053]
[0054] [Where R 1 represents a hydrogen atom or a methyl group. 2 represents an aromatic ring group which may have a substituent, or an alkyl group substituted by an aromatic ring group which may have a substituent. 1 represents a (thio)ester bond, a (thio)carbonate bond, a (thio)amide bond, a (thio)urethane bond, a (thio)urea bond, or a (thio)ether bond, or oxygen, sulfur, or a nitrogen atom which may have a substituent. X 2 represents oxygen, sulfur or a nitrogen atom which may have a substituent. A represents a divalent group which may have a substituent. L represents an (m+1)-valent linking group which may have a substituent. m represents an integer of 1 to 3. n represents 0 or 1.]
[0055] 1-1. About R in Formula (1) 1
[0056] R 1 represents a hydrogen atom or a methyl group. In order to obtain a more polymerizable compound, R 1 Preferred is a hydrogen atom.
[0057] In formula (1), m is 2 or 3, R 1 If there are two or more, two or more R 1 Can be the same or different.
[0058] 1-2. About R in Formula (1) 2
[0059] R 2 represents an aromatic ring group which may have a substituent, or an alkyl group substituted with an aromatic ring group which may have a substituent.2 The aromatic ring contained in may be a condensed ring.
[0060] R 2 The aromatic ring of the alkyl group is roughly divided into an aromatic hydrocarbon ring and an aromatic heterocyclic ring. In addition, the alkyl group substituted by the aromatic ring group which may have a substituent is an aralkyl group or a heteroaralkyl group which may have a substituent on the aromatic ring.
[0061] Examples of the aromatic hydrocarbon ring include a benzene ring, a naphthalene ring, an anthracene ring, a phenanthrene ring, a perylene ring, a tetracene ring, a pyrene ring, a benzopyrene ring, ring, biphenylene ring, triphenylene ring, acenaphthene ring, fluoranthene ring, fluorene ring and the like.
[0062] Examples of the aromatic heterocyclic ring include: an aromatic heterocyclic ring containing one heteroatom, such as a furan ring, a benzofuran ring, a dibenzofuran ring, a naphthofuran ring, a benzonaphthofuran ring, a dinaphthofuran ring, a thiophene ring, a benzothiophene ring, a dibenzothiophene ring, a naphthothiophene ring, a benzonaphthothiophene ring, a dinaphthothiophene ring, a pyrrole ring, an indole ring, a carbazole ring, a pyridine ring, a quinoline ring, an isoquinoline ring; an aromatic heterocyclic ring containing two or more heteroatoms, such as an imidazole ring, a triazole ring, a tetrazole ring, an oxazole ring, a thiazole ring, a pyridazine ring, a pyrimidine ring, a pyrazine ring, a triazine ring, and a thiadiazole ring; a benzoxazole ring, a thieno-oxazole ring, a thiazoloxazole ring, an oxazolo-oxazole ring, a tetrazole-ox ... The ring is a ring formed by condensing two or three aromatic heterocyclic rings containing two or more heteroatoms, such as an oxazole ring, an oxazolimidazole ring, an oxazolopyridine ring, an oxazolopyridazine ring, an oxazolopyrimidine ring, an oxazolopyrazine ring, a naphthooxazole ring, a quinolinolooxazole ring, a dioxazolopyrazine ring, a phenothiazine ring, a benzothiazole ring, a furothiazole ring, a thienothiazole ring, a thiazolothiazole ring, a thiazolimidazole ring, a thienothiadiazole ring, a thiazolothiadiazole ring, a thiazolopyridine ring, a thiazolopyridazine ring, a thiazolopyrimidine ring, a thiazolopyrazine ring, a naphthothiazole ring, a quinolinolothiazole ring, a thianthracene ring, and a phenothiazine ring. These ring structures may be linked to heteroatoms at any position and may also have any substituents.
[0063] Examples of the aralkyl group include benzyl, 2-phenylethyl, and naphthylmethyl. Examples of the heteroaralkyl group include furanylmethyl, thienylmethyl, and benzothienylmethyl. These may have any substituent.
[0064] As R 2 From the perspective of imparting low water absorption, an aromatic hydrocarbon group is preferred, and a naphthyl group, anthracenyl group, and a fluorenyl group are more preferred.
[0065] From the perspective of obtaining a compound with a high refractive index, R 2, preferably a fused aromatic ring group or aromatic heterocyclic group which may have a substituent, and more preferably a fused aromatic group in which two or three rings of an aromatic heterocyclic ring containing a heteroatom are fused.
[0066] As the aromatic heterocyclic group, a sulfur-containing aromatic heterocyclic group is preferred because the refractive index can be increased. In the sulfur-containing aromatic heterocyclic group, as a hetero atom constituting the aromatic heterocycle, at least a sulfur atom is present. As a hetero atom, in addition to the sulfur atom, an oxygen atom, a nitrogen atom, or both an oxygen atom and a nitrogen atom may be present.
[0067] The number of heteroatoms constituting the sulfur-containing aromatic heterocyclic group is preferably 1 to 3, more preferably 1 to 2, from the viewpoint of avoiding coloration and ensuring solubility.
[0068] Examples of the sulfur-containing aromatic heterocyclic group include: aromatic heterocyclic rings containing one sulfur atom such as thiophene ring, benzothiophene ring, dibenzothiophene ring, benzonaphthothiophene ring, dinaphthothiophene ring, thiopyran ring, naphthothiophene ring, dinaphthothiophene ring, dibenzothiopyran ring, etc.; aromatic heterocyclic rings containing two or more sulfur atoms such as thianthrene ring; aromatic heterocyclic rings containing two or more heteroatoms such as thiazole ring, isothiazole ring, benzothiazole ring, naphthothiazole ring, phenothiazine ring, thiazolimidazole ring, thiazolopyridine ring, thiazolopyridazine ring, thiazolopyrimidine ring, dioxazolopyrazine ring, thiazolopyrazine ring, thiazolopyrazine ring, thiazolopyrazole ring, dibenzobenzothiophene ring, thienooxazole ring, thienothiadiazole ring, thiazolopyridine ring, etc. The sulfur-containing aromatic heterocyclic ring may be a monocyclic ring or a condensed ring. The number of rings constituting the condensed ring is preferably 2 to 8, more preferably 2 to 6, and more preferably 2 to 5 from the viewpoint of easy raw material availability and synthesis.
[0069] Among the above structures, from the viewpoint of high refractive index and low coloration, a benzothiazole ring, a dibenzothiophene ring, a benzonaphthothiophene ring, a dinaphthothiophene ring, and a thianthrene ring are preferred, and any one of a benzothiazole ring, a dibenzothiophene ring, and a thianthrene ring is more preferred.
[0070] R 2 It may or may not have a substituent. 2Examples of the substituent that may be possessed include a halogen atom such as chlorine, bromine or iodine, an alkyl group having 1 to 8 carbon atoms, an alkenyl group having 2 to 8 carbon atoms, an alkoxy group having 1 to 8 carbon atoms, a phenyl group, a mesityl group, a tolyl group, a naphthyl group, a cyano group, an acetoxy group, an alkylcarbonyloxy group having 2 to 9 carbon atoms, an alkoxycarbonyl group having 2 to 9 carbon atoms, a sulfamoyl group, an alkylsulfamoyl group having 2 to 9 carbon atoms, an alkylcarbonyl group having 2 to 9 carbon atoms, a phenethyl group, a hydroxyethyl group, an acetamide group, a dialkylaminoethyl group to which an alkyl group having 1 to 4 carbon atoms is bonded, a trifluoromethyl group, an alkylthio group having 1 to 8 carbon atoms, an arylthio group having 6 to 10 carbon atoms, and a nitro group.
[0071] Among them, preferred are an alkyl group having 1 to 8 carbon atoms, an alkoxy group having 1 to 8 carbon atoms, a cyano group, an acetoxy group, an alkylcarbonyloxy group having 2 to 8 carbon atoms, a sulfamoyl group, an alkylsulfamoyl group having 2 to 9 carbon atoms, and a nitro group.
[0072] R 2 It may have an aromatic heterocyclic group as a substituent.
[0073] R 2 The aromatic heterocyclic group which may be present as a substituent is the same as the above R 2 The meanings of the definitions in are the same, and from the aspect of increasing the refractive index, a sulfur-containing aromatic heterocyclic group is preferred. That is, as the sulfur-containing aromatic heterocyclic ring, a benzothiazole ring, a dibenzothiophene ring, a benzonaphthothiophene ring, a dinaphthothiophene ring, or a thianthrene ring is preferred, and any one of a benzothiazole ring, a dibenzothiophene ring, or a thianthrene ring is more preferred.
[0074] Specific examples of the aromatic ring group having a substituent include: aromatic hydrocarbon groups having a substituent, such as biphenyl, benzylphenyl, phenoxyphenyl, binaphthyl, methylthionaphthyl, benzothiazolylphenyl, benzoxazolylphenyl, and dibenzothienylphenyl; aromatic heterocyclic rings having a substituent, such as methoxycarbonylfuranyl, methylthiothienyl, nitrocarbazolyl, methylbenzoxazolyl, methylbenzothiazolyl, methoxybenzothiazolyl, and chlorobenzothiazolyl; and aralkyl groups having a substituent, such as biphenylmethyl, naphthylthioethyl, and fluorenylmethyl.
[0075] 1-3. Regarding X in formula (1) 1
[0076] X 1 represents a (thio)ester bond, a (thio)carbonate bond, a (thio)amide bond, a (thio)urethane bond, a (thio)urea bond or a (thio)ether bond, or oxygen, sulfur or a nitrogen atom which may have a substituent. The group which may substitute on the nitrogen atom is not particularly limited, and preferably includes an alkyl group having 1 to 8 carbon atoms such as a methyl group and an ethyl group, an aromatic hydrocarbon group such as a phenyl group and a naphthyl group.
[0077] From the viewpoint of easy synthesis of the compound of formula (1) and low viscosity, X 1 , oxygen, sulfur, or a nitrogen atom with or without a substituent can be selected, preferably oxygen or sulfur atom. In particular, an oxygen atom that constitutes a compound that can be produced from relatively inexpensive pentaerythritol tribromide can be used.
[0078] From the perspective of improving the polymerizability of the compound of the present invention, X 1 Any of an ester bond, a carbonate bond, an amide bond, a urethane bond, a urea bond, or an ether bond is preferred, and any of an amide bond, a urethane bond, or a urea bond is more preferred.
[0079] In order to increase the refractive index of the compound of the present invention, as X 1 Any of a thioester bond, a thiocarbonate bond, a thioamide bond, a thiocarbamate bond, a thiourea bond, or a thioether bond may be selected.
[0080] 1-4. Regarding X in formula (1) 2
[0081] X 2 represents oxygen, sulfur or a nitrogen atom which may be substituted. The group which may substitute on the nitrogen atom is not particularly limited, and preferably includes alkyl groups having 1 to 8 carbon atoms such as methyl and ethyl, and aromatic hydrocarbon groups such as phenyl and naphthyl.
[0082] About X 2 From the viewpoint of suppressing the water absorption of the compound of the present invention to be low, oxygen or sulfur atoms are preferred, and sulfur atoms which impart a high refractive index to the compound of the present invention are more preferred.
[0083] 1-5. Regarding A in formula (1)
[0084] A represents a divalent group which may have a substituent.
[0085] The divalent group here is a divalent organic group which may have a branch, preferably a divalent organic group having 1 to 8 carbon atoms and may have a branch, more preferably ethylidene, propylidene, methylene, ethylene, propylene, 2-hydroxypropylene, oxypropylene, oxybutylene, 3-oxypentylene, cyclohexylene, phenylene, xylylene, particularly preferably methylene, ethylene, propylene, 2-hydroxypropylene. When the number of carbon atoms of A is 8 or less, the compound of the present invention can achieve a high refractive index, and the viscosity is reduced, and there is a tendency to improve processability.
[0086] Examples of the substituent which A may have include a halogen atom such as chlorine, bromine or iodine, a hydroxyl group, a mercapto group, an alkyl group having 1 to 8 carbon atoms, an alkenyl group having 2 to 8 carbon atoms, an alkoxy group having 1 to 8 carbon atoms, a phenyl group, a mesityl group, a tolyl group, a naphthyl group, a cyano group, an acetoxy group, an alkylcarbonyloxy group having 2 to 9 carbon atoms, an alkoxycarbonyl group having 2 to 9 carbon atoms, a sulfamoyl group, an alkylsulfamoyl group having 2 to 9 carbon atoms, an alkylcarbonyl group having 2 to 9 carbon atoms, a phenethyl group, a hydroxyethyl group, an acetamide group, a dialkylaminoethyl group to which an alkyl group having 1 to 4 carbon atoms is bonded, a trifluoromethyl group, an alkylthio group having 1 to 8 carbon atoms, an arylthio group having 6 to 10 carbon atoms, and a nitro group.
[0087] Among them, preferred are an alkyl group having 1 to 8 carbon atoms, an alkoxy group having 1 to 8 carbon atoms, a cyano group, an acetoxy group, an alkylcarbonyloxy group having 2 to 8 carbon atoms, a sulfamoyl group, an alkylsulfamoyl group having 2 to 9 carbon atoms, a phenyl group, and a naphthyl group.
[0088] 1-6. About m and n in formula (1)
[0089] m represents an integer of 1 to 3. m is preferably 1 or 2, more preferably 1, because the refractive index of the compound of the present invention tends to be further increased.
[0090] n represents 0 or 1. As n increases, the molecular weight of the compound increases, the viscosity of the polymerizable composition of the present invention increases, and the processability may decrease. Therefore, n is preferably 0. When n is 0, the refractive index of the compound of the present invention tends to increase further.
[0091] 1-7. Regarding L in formula (1)
[0092] L is an (m+1)-valent linking group which may have a substituent, and may be appropriately selected according to the purpose of the compound of the present invention.
[0093] As L, a linear, branched, or cyclic linking group may be appropriately selected and adopted, and a chain-like one is preferred from the viewpoint of alleviating steric hindrance around the (meth)acryloyl group in the compound of the present invention.
[0094] As the chain linking group constituting L, when m=1, methylene, ethylene, 1,3-propylene, 1,2-propylene, butylene, 2-hydroxypropylene, oxyethylene, oxypropylene, oxybutylene, oxyhexylene, oxyheptylene, 3-oxopentylene, -CH2CH2NHC(O)-, -CH2CH2OCH2CH2NHC(O)-, -CH2CH2NHC(O)-, -CH2CH2SCH2CH2-, -CH2CH2NHC(S)-, -CH2CH2OCH2CH2NHC(S)-, -CH2CH2SCH2CH2NHC(S)-, -CH2CH2NHC(S)-, etc. can be mentioned, and they can be used in combination. When m=2 or 3, any hydrogen atom in the above chain compound can be substituted by a (meth)acryloyl group, or can be bonded to a (meth)acryloyl group via a branched structure.
[0095] Examples of the substituent which L may have include a halogen atom (a chlorine atom, a bromine atom, an iodine atom), a hydroxyl group, a mercapto group, an alkyl group having 1 to 8 carbon atoms, an alkenyl group having 2 to 8 carbon atoms, an alkoxy group having 1 to 8 carbon atoms, a phenyl group, a mesityl group, a tolyl group, a naphthyl group, a cyano group, an acetoxy group, an alkylcarbonyloxy group having 2 to 9 carbon atoms, an alkoxycarbonyl group having 2 to 9 carbon atoms, a sulfamoyl group, an alkylsulfamoyl group having 2 to 9 carbon atoms, an alkylcarbonyl group having 2 to 9 carbon atoms, a phenethyl group, a hydroxyethyl group, an acetamide group, a dialkylaminoethyl group to which an alkyl group having 1 to 4 carbon atoms is bonded, a trifluoromethyl group, an alkylthio group having 1 to 8 carbon atoms, an arylthio group having 6 to 10 carbon atoms, and a nitro group.
[0096] From the perspective of ensuring the solubility of the compound of the present invention in various media and avoiding coloration, L is preferably an aliphatic hydrocarbon group. In this case, the number of carbon atoms of the aliphatic hydrocarbon group of L is preferably 1 to 8 (excluding the number of carbon atoms of the substituent) because it can suppress the decrease in the refractive index of the compound of the present invention and the increase in the viscosity of the polymerizable composition of the present invention. In addition, from the perspective of alleviating the above-mentioned steric hindrance, the aliphatic hydrocarbon group is preferably a chain.
[0097] For the purpose of increasing the refractive index of the compound of the present invention, a cyclic linking group may also be selected as L. In this case, L may have a monocyclic structure or a condensed ring structure, and the number of rings constituting L is preferably 1 to 4, more preferably 1 to 3, and further preferably 1 to 2. The ring constituting L may not necessarily be aromatic, but in order to ensure that the size occupied in the overall molecule is reduced and a high refractive index is maintained, an aromatic hydrocarbon ring is preferably used. Here, as the aromatic hydrocarbon ring constituting L, a benzene ring, an indene ring, a naphthalene ring, an azulene ring, a fluorene ring, an acenaphthylene ring, an anthracene ring, a phenanthrene ring, a pyrene ring, etc. may be cited.
[0098] In order to improve the polymerizability of the compound of the present invention, at least one of an ester bond, a carbonate bond, an amide bond, a urethane bond, a urea bond or an ether bond may be used in L. In this case, any one of an amide bond, a urethane bond or a urea bond is more preferred.
[0099] For the purpose of increasing the refractive index of the compound of the present invention, L may be any of a thioester bond, a thiocarbonate bond, a thioamide bond, a thiocarbamate bond, a thiourea bond, and a thioether bond.
[0100] 1-8. Molecular weight
[0101] In the compound of the present invention, from the perspective of suppressing the viscosity to a low level and maintaining good processability, the molecular weight is preferably 2000 or less, more preferably 1500 or less. In addition, from the perspective of reducing the shrinkage during polymerization, the molecular weight of the compound of the present invention is preferably 400 or more, more preferably 500 or more, and further preferably 550 or more.
[0102] 1-9. Water solubility
[0103] The compound of the present invention is preferably water-insoluble for reasons such as improving storage stability and preventing deformation due to moisture absorption after curing. "Water-insoluble" herein means that the solubility in water under the conditions of 25° C. and 1 atmosphere is usually 0.1% by mass or less, preferably 0.02% by mass or less, and more preferably 0.01% by mass or less. On the other hand, by having a certain degree of water solubility, it can have the effects of improving dispersibility when polymerizing in water or a polar solvent, improving adhesion to a substrate, etc., so in this case, the solubility in water is preferably 0.1% by mass or more, and more preferably 1% by mass or more.
[0104] In the present invention, by appropriately selecting the structure of the compound represented by formula (1), the water solubility can be set according to the purpose and application.
[0105] 1-10. Relationship between molecular structure and physical properties
[0106] R with an aromatic ring was introduced into three of the four molecular chains of the quaternary carbon of the pentaerythritol skeleton. 2 In the high refractive compound of the present invention, R 2 The three aromatic rings of the polymer are arranged at an appropriate intermolecular distance by the sulfur atom. Therefore, the compound (monomer) before the polymerization reaction shows high solubility in various media represented by organic solvents. On the other hand, in the polymer, the aromatic rings between molecules are arranged nearby by the polymerization reaction, thereby increasing the local aromatic ring density. As a result, the polymer can show a high refractive index.
[0107] Thus, in order to express a high refractive index in a polymer, the polymerization reaction needs to proceed sufficiently.
[0108] In the compound of the present invention, by using an appropriate linking group L to link the high refractive site introduced into the pentaerythritol skeleton to the (meth)acryloyl group as the polymerizable group, steric hindrance around the polymerizable group can be reduced, thereby achieving both high polymerizability and high refractive index.
[0109] In the compound of the present invention represented by formula (1), L, A, X 1 , X 2 The connecting structure is sandwiched between the pentaerythritol backbone and the (meth)acryloyl site and SR 2 The presence of these connecting structures between the sites makes it possible to adjust the physical properties of the compound of the present invention according to its intended use.
[0110] The compound of the present invention has a pentaerythritol skeleton containing a chemically stable quaternary carbon, and thus has thermal stability and chemical stability under all conditions of synthesis, processing and storage.
[0111] 1-11.Exemplary compounds
[0112] Specific examples of the compound of the present invention represented by formula (1) are shown below, but the present invention is not limited to these examples unless the scope of the invention exceeds the scope of the invention.
[0113] Specific examples of the compound represented by m=1 and n=0 in the above formula (1) are as follows.
[0114] [Chemistry 3]
[0115]
[0116] [Chemistry 4]
[0117]
[0118] [Chemistry 5]
[0119]
[0120] [Chemistry 6]
[0121]
[0122] [Chemistry 7]
[0123]
[0124] [Chemistry 8]
[0125]
[0126] [Chemistry 9]
[0127]
[0128] [Chemistry 10]
[0129]
[0130] [Chemistry 11]
[0131]
[0132] In the formula (1), specific examples of the case other than m=1 and n=0 are as follows.
[0133] [Chemistry 12]
[0134]
[0135] 1-12. Synthesis Method
[0136] The compound of the present invention represented by formula (1) can be synthesized by combining various known methods. An example of a method for synthesizing the compound represented by formula (1) is described using the following structural formula.
[0137] <Synthesis Example when n=0 in Formula (1)>
[0138] First, the intermediate (c) is synthesized by coupling reaction of the compound (a) having three Ys with the thiol compound (b) or the disulfide compound (b'), and then the precursor (f) having the linking group L is synthesized by reaction with the compound (d) having a leaving group. The precursor (f) can also be synthesized by using a compound (d') that generates a hydroxyl group by reacting with a nucleophile instead of (d). In addition, after introducing a leaving group into the intermediate (c), the precursor (f) can be reacted with a compound having an amino group and a thiol group X. 3 The precursor (f) is synthesized by reacting with a nucleophile (e).
[0139] By allowing a (meth)acrylating agent (g-1) (acryloyl chloride, acrylic anhydride, acrylic ester, etc.) to act on the precursor (f), the compound (1A) is obtained.
[0140] Compound (1A) can also be directly synthesized by reacting (g-2) into which a (meth)acryloyl group has been introduced in advance with intermediate (c). Compound (1A) can also be synthesized by reacting (h-1) having a leaving group with intermediate (c) to obtain precursor (i) and coupling (meth)acrylic acid (g-3) with the precursor (i).
[0141] In the nucleophile (e), X 3 represents a group selected from hydroxyl, amino and mercapto groups, L and L1 represents a (m+1)-valent group which may or may not have a substituent. Y is a halogen atom, preferably bromine or iodine, but may also be chlorine. 1 ~Y 3 represents any one of a halogen atom, an ester group, a sulfonate group, a carbonate group, and an isocyanate group. Z represents any one of a halogen atom, a carboxyl group, an alkoxy group, and a sulfonyl group.
[0142] [Chemistry 13]
[0143]
[0144] The intermediate (c) can be obtained by allowing the compound (b) in the presence of a base, or the compound (b') in the presence of a base and a reducing agent to act on the compound (a).
[0145] In the synthesis of the intermediate (c), as the organic solvent, dimethoxyethane, tetrahydrofuran, methanol, ethanol, toluene, N,N-dimethylformamide, acetone, water, etc. can be used alone or in combination.
[0146] As the base, triethylamine, pyridine, sodium hydrogen carbonate, sodium carbonate, potassium carbonate, potassium tert-butoxide, etc. can be used alone or in combination.
[0147] As the reducing agent, reducing agents that reduce disulfide bonds to provide thiols, such as sodium formaldehyde sulfoxylate (Rongalite), sodium dithionite, sodium thiosulfate, sodium borohydride, and lithium aluminum hydride, can be used alone or in combination.
[0148] By making all Y of compound (a) and "R 2 -S" part is replaced to obtain intermediate (c). The replacement is carried out successively, so the reaction is stopped after confirming that all the replacements are completed by an appropriate method. Methods for confirming the reaction status of obtaining intermediate (c) include thin layer chromatography, liquid chromatography, gas chromatography, nuclear magnetic resonance measurement, infrared absorption measurement, etc.
[0149] In order to improve the purity of the intermediate (c), column chromatography filled with silica gel may also be used.
[0150] The intermediate (c) thus obtained is reacted with a compound (d) having a linking group L to obtain a precursor (f). The linking reaction between (c) and (d) can be carried out under either acidic or alkaline conditions. In addition, a cross-coupling reaction or free radical coupling using a metal catalyst can also be used. Precursor (f) can also be synthesized by using a compound (d') instead of compound (d). When sulfur or a nitrogen atom with or without a substituent is introduced into X of precursor (f), 1 In the case of3 The precursor (f) can be synthesized by reacting with a nucleophile (e). In this case, the precursor (f) can be obtained by converting the hydroxyl group of the intermediate (c) into a leaving group such as a halogen atom, a sulfonate ester, or an acyl group and then reacting with a nucleophile (e).
[0151] Similar to the case of the intermediate (c), in order to improve the purity of the precursor (f), column chromatography filled with silica gel or recrystallization using an appropriate solvent may be performed.
[0152] When the precursor (f) is coexistent with an organic basic compound such as triethylamine, pyridine or imidazole, or an inorganic basic compound such as sodium carbonate or potassium carbonate, alone or in combination, it reacts with a (meth)acrylating agent (g-1) (acryloyl chloride, acrylic anhydride, acrylic ester, etc.) to obtain compound (1A).
[0153] At this time, as the organic solvent, dimethoxyethane, dichloromethane, tetrahydrofuran, toluene, N,N-dimethylformamide, etc. can be used alone or in combination.
[0154] Similar to the case of the intermediate (c) and the precursor (f), in order to improve the purity of the compound (1A), column chromatography filled with silica gel or recrystallization using an appropriate solvent may be performed.
[0155] Compound (1A) can also be synthesized from compound (j) having leaving groups such as 4 halogen atoms. Precursor (f) can be synthesized by coupling a nucleophile (e) having a group selected from hydroxyl, amino and sulfhydryl groups, and a thiol compound (b) or a disulfide compound (b'). In this case, there is no restriction on the reaction sequence, and the synthesis can be performed in any order and by any method. Compound (1A) can be synthesized by allowing (g-1) to act on precursor (f), which is the same as above.
[0156] Compound (h-2) and thiol compound (b) or disulfide compound (b') are coupled in any order and by any method to obtain compound (i) from compound (j), and compound (1A) can be synthesized by reacting compound (i) with (meth)acrylic acid (g-3).
[0157] [Chemistry 14]
[0158]
[0159] <Synthesis Example in the Case of n=1 in Formula (1)>
[0160] The compound (a) having three Ys on the pentaerythritol skeleton, the compound (k) each having one group selected from hydroxyl, amino and thiol and Y, the thio compound (b), and the compound (g-2) having a (meth)acryloyl group can be synthesized by combining various known methods. For example, the compound (1B) can be synthesized by sequentially coupling the compound (a), the compound (k), the compound (b), and the compound (g-2). The order of these coupling reactions is not limited, and they can be carried out in any order and by any method.
[0161] [Chemistry 15]
[0162]
[0163] 2. Regarding the polymerizable composition of the present invention
[0164] The polymerizable composition of the present invention contains the compound of the present invention represented by formula (1) and a polymerization initiator.
[0165] The (meth)acryloyl group as a polymerizable functional group of the compound of the present invention represented by formula (1) undergoes a polymerization reaction under the action of a polymerization initiator, thereby obtaining the polymer of the present invention.
[0166] 2-1. Polymerization initiator
[0167] The type of polymerization initiator is not particularly limited and can be suitably selected from known polymerization initiators according to the polymerization method. In addition, the polymerization method is also not limited and polymerization can be carried out by known methods such as bulk polymerization, solution polymerization, suspension polymerization, emulsion polymerization, partial polymerization, etc.
[0168] Examples of the polymerization initiator contained in the polymerizable composition of the present invention include radical polymerization initiators, redox polymerization initiators, anionic polymerization initiators, and cationic polymerization initiators. In addition, photocationic polymerization initiators that generate cations as active species upon light irradiation may be used.
[0169] In addition, the examples of polymerization initiators described below also include substances generally called polymerization catalysts.
[0170] 2-1-1. Radical polymerization initiator
[0171] <Photopolymerization Initiator>
[0172] As for the photopolymerization initiator that assists the polymerization of the polymerizable composition of the present invention, any known photoradical polymerization initiator may be used. As examples, azo compounds, azide compounds, organic peroxides, organic borates, onium salts, bisimidazole derivatives, cyclopentadienyl titanium compounds, iodonium salts, organic thiol compounds, halogenated hydrocarbon derivatives, acetophenones, benzophenones, hydroxybenzenes, thioxanthones, anthraquinones, ketals, acylphosphine oxides, sulfone compounds, carbamic acid derivatives, sulfonamides, triarylcarbinols, oxime esters, etc. are used. Among them, as the photopolymerization initiator, benzophenones, acylphosphine oxide compounds, oxime ester compounds, etc. are preferred from the perspectives of compatibility and availability.
[0173] Specific examples of the photopolymerization initiator include benzophenone, 2,4,6-trimethylbenzophenone, methyl o-benzoylbenzoate, 4-phenylbenzophenone, tert-butylanthraquinone, 2-ethylanthraquinone, diethoxyacetophenone, 2-hydroxy-2-methyl-1-phenylpropane-1-one, oligo{2-hydroxy-2-methyl-1-[4-(1-methylvinyl)phenyl]propanone}, benzoin dimethyl ether, 1-hydroxycyclohexylphenyl ketone, benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, benzoin isobutyl ether, 2-methyl-[4-(methylthio)phenyl]-2-morpholino-1-propanone, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)propanone, )-1-butanone, diethyl thioxanthone, isopropyl thioxanthone, 2,4,6-trimethylbenzoyldiphenylphosphine oxide, bis(2,6-dimethoxybenzoyl)-2,4,4-trimethylpentylphosphine oxide, bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide, 2-hydroxy-1-{4-[4-(2-hydroxy-2-methylpropionyl)benzyl]phenyl}-2-methylpropane-1-one and methyl benzoylformate, 1-[4-(phenylthio)-2-(O-benzoyloxime)]-1,2-octanedione, 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazole-3-yl]-1-(O-acetooxime)ethanone, etc.
[0174] These photopolymerization initiators may be used alone or in combination of two or more in any ratio.
[0175] Regarding the content of the photopolymerization initiator in the polymerizable composition of the present invention, when the total amount of all compounds that can be subjected to free radical polymerization in the polymerizable composition is 100 parts by mass, the content is usually 0.01 parts by mass or more, preferably 0.02 parts by mass or more, and more preferably 0.05 parts by mass or more. The upper limit is usually 10 parts by mass or less, preferably 5 parts by mass or less, and more preferably 3 parts by mass or less. If the amount of photopolymerization initiator added is too much, the polymerization proceeds rapidly, which not only increases the birefringence of the cured body, but also may deteriorate the color tone. On the other hand, if the amount added is too little, the polymerizable composition may not be fully polymerized.
[0176] <Thermal Polymerization Initiator>
[0177] As the thermal polymerization initiator that assists the polymerization of the polymerizable composition of the present invention, any known thermal free radical polymerization initiator can be used. Examples thereof include organic peroxides and azo compounds. Among them, organic peroxides are preferred because bubbles are less likely to be generated in the polymer obtained by the polymerization reaction.
[0178] Specific examples of organic peroxides include: ketone peroxides such as methyl ethyl ketone peroxide; peroxyketals such as 1,1-di(tert-hexylperoxy)-3,3,5-trimethylcyclohexane, 1,1-di(tert-hexylperoxy)cyclohexane, and 1,1-di(tert-butylperoxy)cyclohexane; hydroperoxides such as 1,1,3,3-tetramethylbutyl hydroperoxide, cumene hydroperoxide, and terpane hydroperoxide; dialkyl peroxides such as dicumyl peroxide and di-tert-butyl peroxide; diacyl peroxides such as dilauroyl peroxide and dibenzoyl peroxide; peroxydicarbonates such as di(4-tert-butylcyclohexyl)peroxydicarbonate and di(2-ethylhexyl)peroxydicarbonate; and peroxyesters such as tert-butyl peroxy(2-ethylhexanoate), tert-hexyl peroxyisopropylmonocarbonate, tert-butyl peroxybenzoate, and 1,1,3,3-tetramethylbutyl-2-ethylhexanoate.
[0179] Specific examples of the azo compound include 2,2'-azobisisobutyronitrile, 2,2'-azobis(2-methylbutyronitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), 1,1'-azobis-1-cyclohexanecarbonitrile, dimethyl-2,2'-azobisisobutyrate, 4,4'-azobis-4-cyanovaleric acid, and 2,2'-azobis-(2-amidinopropane) dihydrochloride.
[0180] These thermal polymerization initiators may be used alone or in combination of two or more in any ratio.
[0181] Regarding the content of the thermal polymerization initiator in the polymerizable composition of the present invention, when the total amount of all compounds that can be subjected to free radical polymerization in the polymerizable composition is 100 parts by mass, the content is usually 0.1 parts by mass or more, preferably 0.5 parts by mass or more, and more preferably 0.8 parts by mass or more. The upper limit is usually 10 parts by mass or less, preferably 5 parts by mass or less, and more preferably 2 parts by mass or less. If the thermal polymerization initiator is too much, the polymerization proceeds rapidly, which not only impairs the optical uniformity of the obtained polymer, but also may deteriorate the color tone. On the other hand, if the addition amount is too small, the thermal polymerization may not proceed sufficiently.
[0182] When a photopolymerization initiator and a thermal polymerization initiator are used together, the mass ratio thereof is usually "100:1" to "1:100" ("photopolymerization initiator: thermal polymerization initiator", the same applies in the following paragraph), preferably "10:1" to "1:10". If the thermal polymerization initiator is too little, polymerization may be insufficient, and if it is too much, coloring may occur.
[0183] 2-1-2. Redox polymerization initiator
[0184] The redox polymerization initiator is a radical initiator that utilizes a redox reaction based on a combination of a peroxide and a reducing agent, and can generate radicals even at low temperatures, and is generally used in emulsion polymerization and the like.
[0185] Specific examples of redox polymerization initiators include: a combination system of dibenzoyl peroxide as a peroxide and aromatic tertiary amines such as N,N-dimethylaniline, N,N-dimethyl-p-toluidine, and N,N-bis(2-hydroxypropyl)-p-toluidine as a reducing agent; a combination system of hydroperoxide as a peroxide and metal soaps as a reducing agent; a combination system of hydroperoxide as a peroxide and thioureas as a reducing agent, etc.
[0186] In the water-soluble redox polymerization initiator, a peroxide such as persulfate, hydrogen peroxide, or hydroperoxide is mixed with a water-soluble inorganic reducing agent (Fe 2+ , NaHSO3, etc.) or organic reducing agents (alcohols, polyamines, etc.) are used in combination.
[0187] The preferred range of the content of the redox polymerization initiator in the polymerizable composition of the present invention is the same as that of the thermal polymerization initiator.
[0188] 2-1-3. Anionic polymerization initiator
[0189] Examples of the anionic polymerization initiator used in the polymerizable composition of the present invention include alkali metals, n-butyl lithium, sodium amide, sodium naphthalene, Grignard reagents, lithium alkoxides, alkali metal benzophenone ketyl radicals, etc. These may be used alone or in any combination and ratio.
[0190] 2-1-4. Cationic polymerization initiator
[0191] Examples of the cationic polymerization initiator used in the polymerizable composition of the present invention include Bronsted acids such as perchloric acid, sulfuric acid, and trichloroacetic acid; Lewis acids such as boron trifluoride, aluminum trichloride, aluminum tribromide, and tin tetrachloride; iodine, triphenylmethane, etc. These may be used alone or in any combination and ratio.
[0192] The amount of the anionic polymerization initiator or cationic polymerization agent in the polymerizable composition of the present invention is generally 0.001 parts by mass or more, preferably 0.005 parts by mass or more, and more preferably 0.01 parts by mass or more, relative to a total of 100 parts by mass of all compounds that can be anionically or cationically polymerized in the polymerizable composition. The upper limit is generally 5 parts by mass or less, preferably 1 part by mass or less, and more preferably 0.5 parts by mass or less. If the anionic or cationic polymerization initiator is less than 0.001 parts by mass, it will not cause a sufficient reaction; if it is mixed with more than 5 parts by mass, it will be difficult to take into account both the usable time and the polymerization rate.
[0193] 2-1-5. Photocationic polymerization initiator
[0194] The photocationic polymerization initiator in the present invention is an initiator that generates cationic species under the action of light. As the photocationic polymerization initiator, there is no particular limitation as long as it is a compound that generates cationic species under light irradiation, and onium salts are generally well known. As onium salts, diazonium salts of Lewis acids, iodonium salts of Lewis acids, sulfonium salts of Lewis acids, etc. can be cited. Specifically, phenyldiazonium salts of boron tetrafluoride, diphenyliodonium salts of phosphorus hexafluoride, diphenyliodonium salts of antimony hexafluoride, tri-4-methylphenylsulfonium salts of arsenic hexafluoride, tri-4-methylphenylsulfonium salts of antimony tetrafluoride, etc. can be cited. Preferably, aromatic sulfonium salts are used.
[0195] Specific examples of the photocationic polymerization initiator include S,S,S',S'-tetraphenyl-S,S'-(4,4'-thiodiphenyl)disulfonium bishexafluorophosphate, diphenyl-4-phenylthienylsulfonium hexafluorophosphate, diphenyl-4-phenylthienylsulfonium hexafluoroantimonate, and the like. Examples thereof include UVI6992 manufactured by Dow Chemical, CPI-100P manufactured by San-Apro, CPI-101A manufactured by San-Apro, CPI-200K manufactured by San-Apro, and Irgacure 270 manufactured by BASF (Irgacure is a registered trademark of BASF).
[0196] These photocationic polymerization initiators may be used alone or in combination of two or more in any ratio.
[0197] The amount of the photocationic polymerization initiator in the polymerizable composition of the present invention is preferably 0.02 parts by mass to 20 parts by mass, and more preferably 0.1 parts by mass to 10 parts by mass, relative to 100 parts by mass of the total of all compounds capable of photocationic polymerization in the polymerizable composition. If the photocationic polymerization initiator is less than 0.02 parts by mass, a sufficient reaction cannot be induced; if it is mixed in excess of 20 parts by mass, it is difficult to achieve both usable time and polymerization speed.
[0198] When using a photocationic polymerization initiator, the above-mentioned cationic polymerization initiator can be used in combination. In this case, the cationic polymerization initiator is usually used in an amount of 0.1 to 10 parts by mass, preferably 1 to 5 parts by mass, relative to 100 parts by mass of the cationic polymerizable compound in the polymerizable composition. If the amount of the cationic polymerization initiator is too small, the polymerization rate slows down. On the other hand, if the amount is too large, the physical properties of the obtained polymer may be reduced.
[0199] In addition, in the use of the photocationic polymerization initiator, a photocationic polymerization sensitizer can also be used in combination. The photocationic polymerization sensitizer refers to a formula in which the energy of the irradiated light is effectively transferred to the photocationic polymerization initiator by using the photocationic polymerization sensitizer in combination when the irradiated light of the light source used in the photocationic polymerization does not perfectly match the absorption wavelength of the photocationic polymerization initiator. Phenolic compounds such as methoxyphenol (Japanese Patent Publication No. 5-230189), thioxanthone compounds (Japanese Patent Publication No. 2000-204284), and dialkoxy anthracene compounds (Japanese Patent Publication No. 2000-119306) are known.
[0200] The photocationic polymerization sensitizer is usually used in an amount of 0.2 to 5 parts by mass, preferably 0.5 to 1 part by mass, relative to 1 part by mass of the photocationic polymerization initiator. If the amount of the photocationic polymerization sensitizer is too small, the sensitization effect may not be exhibited; on the other hand, if the amount is too large, the physical properties of the polymer may be reduced.
[0201] 2-2. About polymerizable compounds
[0202] The polymerizable compound contained in the polymerizable composition of the present invention may contain any one of the compounds of the present invention represented by formula (1) alone, or may contain two or more of them in any combination and ratio.
[0203] The polymerizable composition of the present invention may contain other polymerizable compounds besides the compound of the present invention.
[0204] The content of the compound of the present invention in the polymerizable composition of the present invention is preferably 1% by mass or more and 99% by mass or less, and particularly preferably 5% by mass or more and 95% by mass or less, based on the total solid content of the polymerizable composition of the present invention. If the content of the compound of the present invention is less than 1% by mass, the effect of using the compound of the present invention cannot be fully exerted; on the other hand, if it exceeds 99% by mass, the curability tends to decrease.
[0205] As examples of other polymerizable compounds, cationic polymerizable monomers, anionic polymerizable monomers, free radical polymerizable monomers, etc. can be enumerated. Any of these polymerizable compounds can be used alone, or two or more can be used in any combination and ratio. In addition, polymerizable compounds (sometimes referred to as multifunctional monomers) having more than two polymerizable functional groups in one molecule can also be used. When using multifunctional monomers, a cross-linked structure is formed inside the polymer, so thermal stability, weather resistance, solvent resistance, etc. can also be improved.
[0206] When the polymerizable composition of the present invention contains other polymerizable compounds other than the compound of the present invention, the content thereof is preferably 0.1% by mass or more and 10% by mass or less, and particularly 0.3% by mass or more and 5% by mass or less, based on the total solid content of the polymerizable composition of the present invention. If the content of other polymerizable compounds is less than 0.1% by mass, the property-imparting effect due to the addition cannot be fully exerted, while if it exceeds 5% by mass, problems such as loss of optical properties and strength tend to occur.
[0207] <Cationically polymerizable monomer>
[0208] Examples of the cationically polymerizable monomer include compounds having an oxirane ring, styrene and its derivatives, vinylnaphthalene and its derivatives, vinyl ethers, N-vinyl compounds, and compounds having an oxetane ring.
[0209] Among them, it is preferred to use at least a compound having an oxetane ring, and it is more preferred to use a compound having an oxetane ring and a compound having an oxirane ring in combination.
[0210] The compound having an ethylene oxide ring may be a prepolymer having two or more ethylene oxide rings in one molecule.
[0211] Examples of such prepolymers include alicyclic polyepoxides, polyglycidyl esters of polyacids, polyglycidyl ethers of polyols, polyglycidyl ethers of polyoxyalkylene glycols, polyglycidyl ethers of aromatic polyols, hydrogenated compounds of polyglycidyl ethers of aromatic polyols, urethane polyepoxides, and epoxidized polybutadienes.
[0212] Examples of styrene and derivatives thereof include styrene, p-methylstyrene, p-methoxystyrene, β-methylstyrene, p-methyl-β-methylstyrene, α-methylstyrene, p-methoxy-β-methylstyrene, and divinylbenzene.
[0213] Examples of vinylnaphthalene and derivatives thereof include 1-vinylnaphthalene, α-methyl-1-vinylnaphthalene, β-methyl-1-vinylnaphthalene, 4-methyl-1-vinylnaphthalene, and 4-methoxy-1-vinylnaphthalene.
[0214] Examples of the vinyl ethers include isobutyl ether, ethyl vinyl ether, phenyl vinyl ether, p-methylphenyl vinyl ether, and p-methoxyphenyl vinyl ether.
[0215] Examples of the N-vinyl compound include N-vinylcarbazole, N-vinylpyrrolidone, N-vinylindole, N-vinylpyrrole, and N-vinylphenothiazine.
[0216] Examples of the compound having an oxetane ring include various known oxetane compounds described in JP-A Nos. 2001-220526 and 2001-310937.
[0217] These cationically polymerizable monomers may be used alone or in combination of two or more in any ratio.
[0218] <Anionic polymerizable monomer>
[0219] Examples of the anionic polymerizable monomer include hydrocarbon monomers and polar monomers.
[0220] Examples of the hydrocarbon monomer include styrene, α-methylstyrene, butadiene, isoprene, vinylpyridine, vinylanthracene, and derivatives thereof.
[0221] Examples of polar monomers include methacrylates (e.g., methyl methacrylate, ethyl methacrylate, isopropyl methacrylate, etc.); acrylates (e.g., methyl acrylate, ethyl acrylate, etc.); vinyl ketones (e.g., methyl vinyl ketone, isopropyl vinyl ketone, cyclohexyl vinyl ketone, phenyl vinyl ketone, etc.); isopropenyl ketones (e.g., methyl isopropenyl ketone, phenyl isopropenyl ketone, etc.); other polar monomers (e.g., acrylonitrile, acrylamide, nitroethylene, methylene malonate, cyanoacrylate, vinylidene cyanide, etc.), etc.
[0222] These anionic polymerizable monomers may be used alone or in combination of two or more in any ratio.
[0223] <Radical polymerizable monomer>
[0224] The radical polymerizable monomer is a compound having one or more ethylenically unsaturated double bonds in one molecule, and examples thereof include (meth)acrylates, (meth)acrylamides, vinyl esters, and styrenes.
[0225] Examples of (meth)acrylates include methyl (meth)acrylate, ethyl (meth)acrylate, (n- or iso-)propyl (meth)acrylate, (n-, iso-, sec- or tert-)butyl (meth)acrylate, pentyl (meth)acrylate, adamantyl (meth)acrylate, chloroethyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxypentyl (meth)acrylate, cyclohexyl (meth)acrylate, allyl (meth)acrylate, trimethylolpropane mono(meth)acrylate, pentaerythritol mono(meth)acrylate, benzyl (meth)acrylate, methoxybenzyl (meth)acrylate, chlorobenzyl (meth)acrylate, Hydroxybenzyl (meth)acrylate, hydroxyphenylethyl (meth)acrylate, dihydroxyphenylethyl (meth)acrylate, furfuryl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, phenyl (meth)acrylate, hydroxyphenyl (meth)acrylate, chlorophenyl (meth)acrylate, sulfamoylphenyl (meth)acrylate, 2-phenoxyethyl (meth)acrylate, 2-(hydroxyphenylcarbonyloxy)ethyl (meth)acrylate, phenol EO-modified (meth)acrylate, phenylphenol EO-modified (meth)acrylate, p-cumylphenol EO-modified (meth)acrylate, nonylphenol EO-modified (meth)acrylate, N-acryloyloxyethyl hexahydrophthalimide, bisphenol F EO modified diacrylate, bisphenol A EO modified diacrylate, dibromophenyl (meth)acrylate, tribromophenyl (meth)acrylate, biscyclopentenyloxyethyl (meth)acrylate, biscyclopentyl acrylate, tricyclodecane dimethanol di(meth)acrylate, bisphenoxyethanol fluorene di(meth)acrylate, trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, etc. "EO" here means "ethylene oxide".
[0226] Examples of (meth)acrylamides include (meth)acrylamide, N-methyl(meth)acrylamide, N-ethyl(meth)acrylamide, N-propyl(meth)acrylamide, N-butyl(meth)acrylamide, N-benzyl(meth)acrylamide, N-hydroxyethyl(meth)acrylamide, N-phenyl(meth)acrylamide, N-tolyl(meth)acrylamide, N-(hydroxyphenyl)(meth)acrylamide, N-(sulfamoylphenyl)(meth)acrylamide, N-(benzenesulfonyl)(meth)acrylamide, N-(tolylsulfonyl)(meth)acrylamide, N,N-dimethyl(meth)acrylamide, N-methyl-N-phenyl(meth)acrylamide, and N-hydroxyethyl-N-methyl(meth)acrylamide.
[0227] Examples of vinyl esters include vinyl acetate, vinyl butyrate, vinyl benzoate, vinyl benzoate, vinyl tert-butyl benzoate, vinyl chlorobenzoate, vinyl 4-ethoxybenzoate, vinyl 4-ethylbenzoate, vinyl 4-methylbenzoate, vinyl 3-methylbenzoate, vinyl 2-methylbenzoate, vinyl 4-phenylbenzoate, and vinyl pivalate.
[0228] Examples of styrenes include styrene, p-acetyl styrene, p-benzoyl styrene, 2-butoxymethyl styrene, 4-butyl styrene, 4-sec-butyl styrene, 4-tert-butyl styrene, 2-chlorostyrene, 3-chlorostyrene, 4-chlorostyrene, dichlorostyrene, 2,4-diisopropylstyrene, dimethylstyrene, p-ethoxystyrene, 2-ethylstyrene, 2-methoxystyrene, 4-methoxystyrene, 2-methylstyrene, 3-methylstyrene, 4-methylstyrene, p-methylstyrene, p-phenoxystyrene, p-phenylstyrene, and divinylbenzene.
[0229] These radical polymerizable monomers may be used alone or in combination of two or more in any ratio.
[0230] The cationically polymerizable monomers, anionic polymerizable monomers, and radical polymerizable monomers exemplified above may be used alone or in combination of two or more.
[0231] In the application of holographic recording media, it is preferred to use a radical polymerizable monomer as the other polymerizable compound used in combination with the compound of the present invention represented by formula (1) because the reaction for forming the resin matrix is less likely to be inhibited.
[0232] 2-3 Other added ingredients
[0233] The polymerizable composition of the present invention may contain other components within a range that does not impair the effects of the present invention.
[0234] As other components, various additives such as solvents, antioxidants, plasticizers, ultraviolet absorbers, sensitizers, chain transfer agents, defoamers, polymerization inhibitors, any fillers composed of organic or inorganic substances, dispersants, pigments, wavelength conversion materials such as phosphors, etc. can be cited.
[0235] The polymerizable composition of the present invention may contain a solvent for adjusting the viscosity.
[0236] Specific examples of the solvent include, depending on the physical properties of the polymerizable composition, alcohols such as ethanol, propanol, isopropanol, ethylene glycol, and propylene glycol; aliphatic hydrocarbons such as hexane, pentane, and heptane; alicyclic hydrocarbons such as cyclopentane and cyclohexane; aromatic hydrocarbons such as toluene and xylene; halogenated hydrocarbons such as dichloromethane and chloroform; chain ethers such as dimethyl ether and diethyl ether; cyclic ethers such as dioxane and tetrahydrofuran; esters such as methyl acetate, ethyl acetate, butyl acetate, ethyl lactate, and ethyl butyrate; acetone, ethyl methyl ketone, methyl isobutyl ketone, and the like. Ketones such as acetone and cyclohexanone; cellosolves such as methyl cellosolve, ethyl cellosolve and butyl cellosolve; carbitols such as methyl carbitol, ethyl carbitol and butyl carbitol; propylene glycol monoalkyl ethers such as propylene glycol monomethyl ether, propylene glycol monoethyl ether and propylene glycol mono-n-butyl ether; glycol ether esters such as ethylene glycol monomethyl ether acetate and propylene glycol monomethyl ether acetate; amides such as N,N-dimethylformamide and N,N-dimethylacetamide; sulfoxides such as dimethyl sulfoxide; nitriles such as acetonitrile and benzonitrile; organic solvents such as N-methylpyrrolidone.
[0237] These solvents may be used alone or as a mixed solvent. In addition, water may also be used depending on the polymerization method (emulsion polymerization, suspension polymerization, etc.).
[0238] When a solvent (or dispersion medium) is used, the amount thereof is not particularly limited, and may be adjusted so as to obtain a polymerizable composition having an appropriate viscosity depending on the polymerization method, processing method, and application.
[0239] In the present invention, in order to improve the heat yellowing resistance of the obtained polymer, it is preferred to mix an antioxidant as an additive in the polymerizable composition.
[0240] Specific examples of antioxidants include phenolic antioxidants such as 2,6-di-tert-butylphenol, 2,6-di-tert-butyl-p-cresol, 3-(3',5'-di-tert-butyl-4'-hydroxyphenyl) propionate, tetrakis-[methylene-3-(3',5'-di-tert-butyl-4'-hydroxyphenyl) propionate]methane, triethylene glycol bis[3-(3-tert-butyl-5-methyl-4-hydroxyphenyl) propionate], and 1,6-hexanediol bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate]; and phosphorus antioxidants such as triphenyl phosphite, triisodecyl phosphite, tris(tridecyl) phosphite, and tris(2,4-di-tert-butylphenyl) phosphite. These antioxidants may be used alone or in combination of two or more.
[0241] As the antioxidant, it is preferred to use a phenolic antioxidant in combination with a phosphorus antioxidant. As a preferred combination of a phenolic antioxidant and a phosphorus antioxidant, there can be cited a combination of at least one selected from tetrakis-[methylene-3-(3',5'-di-tert-butyl-4'-hydroxyphenyl)propionate]methane and 3-(3',5'-di-tert-butyl-4'-hydroxyphenyl)propionate n-octadecyl alcohol ester as a phenolic antioxidant and tris(2,4-di-tert-butylphenyl)phosphite as a phosphorus antioxidant.
[0242] The amount of the antioxidant in the polymerizable composition of the present invention is preferably 0.01 to 5 parts by mass, more preferably 0.05 to 3 parts by mass, and even more preferably 0.1 to 2 parts by mass based on 100 parts by mass of the total amount of the polymerizable composition, from the viewpoint of improving the heat yellowing resistance of the obtained polymer.
[0243] 2-4 Method for producing polymerizable composition
[0244] The polymerizable composition of the present invention may be produced by mixing the components, or may be produced by preliminarily mixing the components other than the polymerization initiator and then adding the polymerization initiator immediately before the polymerization reaction.
[0245] 3. Polymerization method of the polymerizable composition of the present invention
[0246] The polymerization method of the polymerizable composition of the present invention is not particularly limited, and there are a method of polymerizing by irradiating an active energy ray and a method of polymerizing by heating.
[0247] 3-1. Polymerization initiation method (active energy rays)
[0248] When the polymerizable composition of the present invention is subjected to photoradical polymerization, polymerization is carried out by irradiation with active energy rays.
[0249] As the active energy ray used, electron beams or light in the wavelength range from ultraviolet to infrared are preferred. As the light source, for example, if the active energy ray is ultraviolet light, an ultrahigh pressure mercury light source or a metal halide light source can be used, if it is visible light, a metal halide light source or a halogen light source can be used, and if it is infrared light, a halogen light source can be used. In addition, light sources such as lasers and LEDs can also be used.
[0250] The irradiation amount of the active energy ray is appropriately set according to the type of light source, the film thickness of the coating film, etc., and is preferably appropriately set in a manner such that the total reaction rate of the polymerizable functional groups of the compound of the present invention represented by formula (1) and other polymerizable compounds is 80% or more, more preferably 90% or more. The reaction rate is calculated based on the change in the absorption peak intensity of the polymerizable functional groups before and after the reaction using infrared absorption spectra.
[0251] After polymerization by irradiation with active energy rays, further polymerization may be performed by heating treatment or annealing treatment as needed. The heating temperature at this time is preferably in the range of 80 to 200° C. The heating time is preferably in the range of 10 to 60 minutes.
[0252] 3-2. Polymerization initiation method (heating)
[0253] When heat treatment is performed for polymerization of the polymerizable composition of the present invention, the heating temperature is preferably in the range of 80 to 200° C., more preferably in the range of 100 to 150° C. If the heating temperature is lower than 80° C., the heating time needs to be prolonged, which tends to be uneconomical; if the heating temperature is higher than 200° C., energy costs are incurred, and heating and cooling time are required, which tends to be uneconomical.
[0254] 4. Polymer
[0255] Next, the polymer of the present invention obtained by polymerizing the polymerizable composition of the present invention will be described.
[0256] 4-1. Refractive index
[0257] Generally, the overall density increases through polymerization, so the refractive index of a polymer tends to be higher than that of the compound (called a monomer) before polymerization as its precursor. The refractive index of the resulting polymer can be increased by fully carrying out the polymerization reaction using a monomer with a high refractive index, so it is considered important to increase the refractive index of a polymer by designing the molecular structure of the monomer.
[0258] Regarding the refractive index, when it is evaluated with short-wavelength irradiation light, it shows a larger value; however, a sample that shows a relatively large refractive index at a short wavelength still shows a relatively large refractive index at a long wavelength, and the relationship does not reverse. Therefore, by comparing the refractive index at a certain wavelength, the actual refractive index of the material can be compared. In the present invention, the value at the irradiation light wavelength of 587nm is used as the reference.
[0259] The refractive index of the polymer of the present invention is preferably 1.55 or more, more preferably 1.60 or more, particularly preferably 1.63 or more, and most preferably 1.65 or more. The upper limit of the refractive index of the polymer of the present invention is not particularly limited, but is usually 2.0 or less.
[0260] When the polymer of the present invention is used as an optical material of a lens, etc., if the refractive index is less than 1.55, the central portion of the optical lens, etc. is thickened, and the lightness characteristic of the plastic may be impaired, which is not preferred. In addition, in the development of precision optical components such as lenses, it is also important to achieve optical properties suitable for the components by combining optical materials with more than two refractive indices. From this perspective, a polymer having a refractive index greater than 1.63 can be said to be a particularly useful material suitable for optical components.
[0261] When the polymer of the present invention is used as a recording layer material of a holographic recording medium, the refractive index of the polymer of the present invention is usually in the range of 1.68 or more and 1.78 or less, preferably 1.77 or less. If the refractive index is less than 1.68, the diffraction efficiency is low and the multiplicity is insufficient. In addition, if the refractive index is greater than 1.78, the difference in refractive index with the matrix resin becomes too large, the scattering increases, and the transmittance is reduced, and a larger amount of energy is required during recording and reproducing.
[0262] 4-2. Glass transition temperature
[0263] The glass transition temperature of the polymer of the present invention is preferably 90°C or more, more preferably 100°C or more, further preferably 110°C or more, particularly preferably 120°C or more, and preferably 250°C or less, more preferably 220°C or less, and further preferably 200°C or less. If the glass transition temperature is lower than this range, the optical properties may change from the designed values under the use environment, and the heat resistance required for practical use may not be satisfied. In addition, if the glass transition temperature is higher than this range, the processability of the polymer is reduced, and a molded product with good appearance and high dimensional accuracy may not be obtained. In addition, the polymer becomes brittle, the mechanical strength is reduced, and the handling property of the molded product may be deteriorated.
[0264] 5. Optical materials and optical components
[0265] The compound, polymerizable composition and polymer of the present invention have properties such as high refractive index, easy processability and low shrinkage, and therefore can be suitably used in various optical materials and optical parts.
[0266] Examples of the optical material include optical overcoats, hard coat agents, adhesives for optical components, resins for optical fibers, and acrylic resin modifiers.
[0267] As optical components, there can be mentioned lenses, filters, diffraction gratings, prisms, light guides, cover glass for display devices, optical sensors, photoelectric switches, LEDs, light emitting elements, optical waveguides, optical splitters, optical fiber adhesives, substrates for display elements, substrates for color filters, substrates for touch panels, polarizers, display backlights, light guide plates, anti-reflection films, viewing angle expansion films, optical recording, optical shaping, optical relief printing, etc.
[0268] In addition, it can also be used as these layers. For example, a display protection film etc. can be mentioned.
[0269] Among these, the high refractive index characteristics of the polymer of the present invention are particularly preferred for plastic lenses. As lenses, imaging lenses, eyeglass lenses, beam focusing lenses, light diffusion lenses, etc., of cameras (car-mounted cameras, digital cameras, cameras for PCs, cameras for mobile phones, surveillance cameras, etc.) can be cited.
[0270] In the lens using the polymer of the present invention, in order to improve anti-reflection, impart high hardness, improve abrasion resistance, improve chemical resistance, impart anti-fogging properties, or impart fashionability when necessary, physical or chemical treatments such as surface grinding, antistatic treatment, hard coating treatment, anti-reflective coating treatment, and dyeing treatment can be implemented.
[0271] 6. Holographic recording media
[0272] The polymerizable composition of the present invention can be suitably used for the recording layer of a holographic recording medium. In this case, the polymerizable composition of the present invention is preferably a photoreactive composition containing a matrix resin, a photopolymerization initiator, and a radical scavenger in addition to the compound of the present invention. The following describes the details of the use of the polymerizable composition as a material for a holographic recording medium.
[0273] 6-1. About base resin
[0274] The polymerizable composition of the present invention preferably contains a matrix resin. In particular, the matrix resin constituting the recording layer of the holographic recording medium is an organic substance that does not undergo significant chemical and physical changes due to irradiation with light and is mainly composed of a polymer of an organic compound.
[0275] The matrix resin, together with the above-mentioned polymerizable compound, the photopolymerization initiator described later, etc., constitute the polymerizable composition of the present invention, and therefore it is strongly required to have excellent compatibility with the polymerizable compound, the photopolymerization initiator, etc. If the compatibility of the matrix resin with the above-mentioned other components is low, an interface is formed between the materials, and the light leaks to unnecessary parts due to the refraction or reflection of the light at the interface, so that the interference fringes may be distorted or cut and recorded in inappropriate parts, which may cause the degradation of information. Regarding the compatibility of the matrix resin with the above-mentioned other components, for example, as described in Japanese Patent Gazette No. 3737306, a detector can be set for the sample in a direction different from the transmitted light, and the scattered light intensity obtained thereby can be evaluated.
[0276] As the matrix resin of the polymerizable composition of the present invention, a resin composed of a plurality of materials soluble in a solvent in the polymerizable composition and three-dimensionally cross-linked after being formed into a use state can be used, for example, the thermoplastic resin, thermosetting resin, and photocurable resin described below.
[0277] The three-dimensionally cross-linked resin is solvent-insoluble and is a reaction solidified product of a polymerizable compound that is liquid at room temperature and a compound that is reactive with the polymerizable compound. The three-dimensionally cross-linked resin will become a physical barrier, so the volume change during recording can be suppressed. That is, in the recording layer after recording, the bright part expands and the dark part shrinks, which has a tendency to produce unevenness on the surface of the holographic recording medium. In order to suppress this volume change, it is more preferable to use a polymerizable composition containing a three-dimensionally cross-linked resin matrix in the recording layer.
[0278] Among them, thermosetting resins are preferred as the matrix resin from the viewpoint of adhesion to the support. The resin materials that can be used as the matrix resin are described in detail below.
[0279] 6-1-1. Thermoplastic resin
[0280] Specific examples of the thermoplastic resin include chlorinated polyethylene, polymethyl methacrylate resin (PMMA), copolymers of methyl methacrylate and other alkyl acrylates, copolymers of vinyl chloride and acrylonitrile, polyvinyl acetate resin (PVAC), polyvinyl alcohol, polyvinyl formal, polyvinyl pyrrolidone, cellulose resins such as ethyl cellulose and nitrocellulose, polystyrene resins, polycarbonate resins, etc. These may be used alone or in combination of two or more.
[0281] The solvent for these thermoplastic resins is not particularly limited as long as it can dissolve these resins, and examples thereof include ketones such as acetone and methyl ethyl ketone, esters such as butyl acetate and propylene glycol methyl ether acetate, aromatic hydrocarbons such as toluene and xylene, ethers such as tetrahydrofuran and 1,2-dimethoxyethane, and amides such as N,N-dimethylacetamide and N-methylpyrrolidone. These may be used alone or in combination of two or more.
[0282] 6-1-2. Thermosetting resin
[0283] When a thermosetting resin is used as the matrix resin, the curing temperature varies depending on the type of the crosslinking agent or the catalyst.
[0284] Representative examples of functional group combinations that cure at room temperature include epoxide and amine, epoxide and thiol, and isocyanate and amine. In addition, representative examples of combinations using catalysts include epoxide and phenol, epoxide and acid anhydride, and isocyanate and polyol.
[0285] In the former case, the reaction occurs immediately when mixing, so it is simple; however, in the case of molding such as holographic recording media, it is difficult to adjust because time is insufficient. On the other hand, in the latter case, the curing temperature and curing time can be freely selected by appropriately selecting the type and amount of the catalyst, so it is suitable when curing is performed simultaneously with molding such as holographic recording media. Various types of resin raw materials from low molecular weight to high molecular weight are commercially available, so they can be selected while maintaining compatibility with polymerizable reactive compounds or photoinitiators, adhesion to substrates, etc.
[0286] Each raw material will be described below, but any raw material may be used alone or in combination of two or more.
[0287] <Epoxide>
[0288] Examples of epoxides include polyglycidyl ether compounds of polyols such as (poly)ethylene glycol, (poly)propylene glycol, (poly)tetramethylene glycol, trimethylolpropane, and glycerol, alicyclic epoxy compounds having a 4- to 7-membered cyclic aliphatic group such as 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexylcarboxylate and 3,4-epoxy-1-methylcyclohexyl-3,4-epoxy-1-methylhexanecarboxylate, bisphenol A type epoxy compounds, hydrogenated bisphenol A type epoxy compounds, bisphenol F type epoxy compounds, and phenol or cresol novolac type epoxy compounds.
[0289] Epoxide preferably has 2 or more epoxy groups in 1 molecule, and there is no particular restriction on its type. If the number of epoxy groups is small, the hardness required as a matrix may not be obtained. The upper limit of the number of epoxy groups in 1 molecule is not particularly limited, and is usually 8 or less, preferably 4 or less. If the number of epoxy groups is too much, the consumption of epoxy groups requires a lot of time, and the formation of the matrix resin may take too long.
[0290] <Amine>
[0291] As the amine, a substance containing a primary or secondary amine group can be used. Examples of such amines include aliphatic polyamines such as ethylenediamine, diethylenetriamine or derivatives thereof, alicyclic polyamines such as isophoronediamine, menthanediamine, N-aminoethylpiperazine or derivatives thereof, aromatic polyamines such as meta-xylylenediamine, diaminodiphenylmethane or derivatives thereof, polyamides such as condensates of dicarboxylic acids such as dimer acid and the above polyamines, imidazole compounds such as 2-methylimidazole or derivatives thereof, and dicyandiamide, adipic acid dihydrazide, etc. other than these.
[0292] <Mercaptan>
[0293] Examples of the thiol include thiol compounds such as dithiols such as 1,3-butandithiol, 1,4-butandithiol, 2,3-butandithiol, 1,2-benzenedithiol, 1,3-benzenedithiol, 1,4-benzenedithiol, 1,10-decanedithiol, 1,2-ethanedithiol, 1,6-hexanedithiol, and 1,9-nonandithiol, and polythiols such as Thiokol (manufactured by Toray Fine Chemicals) and jERCURE QX40 (manufactured by Mitsubishi Chemical Corporation). Among them, commercially available fast-curing polythiols such as jERCURE QX40 are preferably used.
[0294] <Phenol>
[0295] Examples of the phenol include bisphenol A, novolac-type phenol resins, and resol-type phenol resins.
[0296] <Anhydride>
[0297] As the acid anhydride, examples of monofunctional acid anhydrides include phthalic anhydride, tetrahydrophthalic anhydride or derivatives thereof, and examples of difunctional acid anhydrides include pyromellitic dianhydride, benzophenonetetracarboxylic anhydride or derivatives thereof.
[0298] <Amount of amine, thiol, phenol, and anhydride>
[0299] The amount of amine, thiol, phenol, and acid anhydride used is usually 0.1 equivalent or more, especially 0.7 equivalent or more, and usually 2.0 equivalent or less, especially 1.5 equivalent or less, in terms of the ratio to the molar number of epoxy groups. If the amount of amine, thiol, phenol, and acid anhydride used is too small or too large, the number of unreacted functional groups increases, and storage stability may be impaired.
[0300] <Polymerization initiator for thermosetting resin>
[0301] As a catalyst for curing the thermosetting resin, an anionic polymerization initiator and a cationic polymerization initiator can be used depending on the curing temperature and the curing time.
[0302] Anionic polymerization initiators are substances that generate anions by heat or active energy ray irradiation, and examples thereof include amines. Examples of amines include amino compounds such as dimethylbenzylamine, dimethylaminomethylphenol, and 1,8-diazabicyclo[5.4.0]undecene-7 and their derivatives; imidazole compounds such as imidazole, 2-methylimidazole, and 2-ethyl-4-methylimidazole and their derivatives. One or more of these can be used depending on the curing temperature and curing time.
[0303] The cationic polymerization initiator is a substance that generates cations by heat or active energy ray irradiation, and examples thereof include aromatic onium salts. As a specific example, SbF6 - 、BF4 - 、AsF6 - PF6 - CF3SO3 - 、B(C6F5)4 - Compounds composed of anionic components such as iodine, sulfur, nitrogen, phosphorus and aromatic cationic components. Among them, diaryliodonium salts and triarylsulfonium salts are preferred. They can be used alone or in combination according to the curing temperature and curing time.
[0304] The amount of these thermosetting resin polymerization initiators is preferably usually more than 0.001 mass %, especially more than 0.01 mass %, and usually less than 50 mass %, especially less than 10 mass % relative to the matrix resin. If the amount of these thermosetting resin polymerization initiators is too little, the concentration of the thermosetting resin polymerization initiator is too low, so the polymerization reaction may take too much time. On the other hand, if the amount of the thermosetting resin polymerization initiator is too much, as the polymerization reaction, continuous ring-opening reaction sometimes does not occur.
[0305] <Isocyanate>
[0306] As isocyanate, it is preferred to have two or more isocyanate groups in one molecule, and there is no particular restriction on its type. If the number of isocyanate groups in one molecule is small, the hardness required as the matrix resin may not be obtained. The upper limit of the number of isocyanate groups in one molecule is not particularly limited, and it is preferably usually 8 or less, especially 4 or less. If the number of isocyanate groups in one molecule is too much, the consumption of isocyanate groups requires a lot of time, and the formation of the matrix resin may take too much time. The upper limit of the number of isocyanate groups in one molecule is not particularly limited, and it is usually 20 or less.
[0307] Examples of isocyanates include aliphatic isocyanates such as hexamethylene diisocyanate, lysine methyl ester diisocyanate, and 2,4,4-trimethylhexamethylene diisocyanate; alicyclic isocyanates such as isophorone diisocyanate and 4,4'-methylenebis(cyclohexyl isocyanate); aromatic isocyanates such as toluene diisocyanate, 4,4'-diphenylmethane diisocyanate, xylylene diisocyanate, and naphthalene-1,5'-diisocyanate; and polymers thereof, among which tri- to heptamers are preferred.
[0308] In addition, water, reaction products of polyols such as trimethylolethane and trimethylolpropane and the above-mentioned isocyanates, and polymers of hexamethylene diisocyanate or derivatives thereof can be mentioned.
[0309] The molecular weight of the isocyanate is preferably 100 to 50,000, more preferably 150 to 10,000, and further preferably 150 to 5,000, in terms of number average molecular weight. If the number average molecular weight is too small, the hardness of the matrix resin becomes too high due to the increase in crosslinking density, which may reduce the recording speed. In addition, if the number average molecular weight is too large, the compatibility with other components is reduced, the crosslinking density is reduced, and the hardness of the matrix resin becomes too low, and the recorded content may disappear.
[0310] <Polyol>
[0311] Examples of the polyol include polypropylene polyol, polycaprolactone polyol, polyester polyol, and polycarbonate polyol.
[0312] (Polypropylene polyol)
[0313] Polypropylene polyol is obtained by the reaction of propylene oxide with a diol or a polyol. As diols or polyols, for example, ethylene glycol, propylene glycol, 1,4-butanediol, 1,5-pentanediol, 3-methyl-1,5-pentanediol, 1,6-hexanediol, neopentyl glycol, diethylene glycol, 1,4-cyclohexanediol, 1,4-cyclohexanedimethanol, decanediol, polyethylene glycol, polytetramethylene glycol, etc. As polypropylene polyol, commercial products thereof include SaniX GP-400, GP-1000 (both manufactured by Sanyo Chemical Co., Ltd., trade names), ADEKA Polyether G400, G700, G1500 (all manufactured by ADEKA, trade names), etc.
[0314] (Polycaprolactone polyol)
[0315] Polycaprolactone polyol is obtained by the reaction of a lactone with a diol or a polyol. Examples of the lactone include α-caprolactone, β-caprolactone, γ-caprolactone, ε-caprolactone, α-methyl-ε-caprolactone, and β-methyl-ε-caprolactone.
[0316] Examples of the diol or polyol include ethylene glycol, propylene glycol, 1,4-butanediol, 1,5-pentanediol, 3-methyl-1,5-pentanediol, 1,6-hexanediol, neopentyl glycol, diethylene glycol, 1,4-cyclohexanediol, 1,4-cyclohexanedimethanol, decanediol, polyethylene glycol, and polytetramethylene glycol.
[0317] As the polycaprolactone polyol obtained by the reaction of ε-caprolactone, commercially available products include PLACCEL 205, PLACCEL 205U, PLACCEL 205UT, PLACCEL 210, PLACCEL 220, PLACCEL 230, PLACCEL 240, PLACCEL 303, PLACCEL 305, PLACCEL 308, PLACCEL 312, PLACCEL 320, PLACCEL 401, PLACCEL 205AL, PLACCEL L212AL, PLACCEL L220AL, PLACCEL L320AL, PLACCEL T2103, PLACCEL T2205, and PLACCEL P3403 (all manufactured by Daicel, trade names).
[0318] (Polyester polyol)
[0319] Examples of the polyester polyol include those obtained by polycondensation of dicarboxylic acids or their anhydrides and polyols.
[0320] Examples of the dicarboxylic acid include succinic acid, adipic acid, sebacic acid, azelaic acid, dimer acid, maleic anhydride, isophthalic acid, terephthalic acid, and trimellitic acid.
[0321] Examples of the polyol include ethylene glycol, propylene glycol, 1,4-butanediol, 1,5-pentanediol, 3-methyl-1,5-pentanediol, 1,6-hexanediol, neopentyl glycol, diethylene glycol, 1,4-cyclohexanediol, 1,4-cyclohexanedimethanol, decanediol, polyethylene glycol, and polytetramethylene glycol.
[0322] Examples of the polyester polyol include polyethylene adipate, polybutylene adipate, polyhexylene adipate, etc. Examples of the polyester polyol include commercially available products such as ADEKA NEWACE F series, ADEKA NEWACE Y series, ADEKA NEWACE NS series (manufactured by ADEKA, trade names), KURARAY Polyol N-2010, P-4011, and P-1020 (all manufactured by KURARAY, trade names), etc.
[0323] (Polycarbonate polyol)
[0324] Examples of the polycarbonate polyol include those obtained by a dealcoholization condensation reaction of a glycol and a dialkyl carbonate (e.g., dimethyl carbonate, diethyl carbonate, etc.), those obtained by a dephenolization condensation reaction of a glycol and a diphenyl carbonate, and those obtained by a dealcoholization condensation reaction of a glycol and a carbonate (e.g., ethylene carbonate, diethyl carbonate, etc.).
[0325] Examples of the diols include aliphatic diols such as 1,6-hexanediol, diethylene glycol, propylene glycol, 1,4-butanediol, 3-methyl-1,5-pentanediol, and neopentyl glycol; and alicyclic diols such as 1,4-cyclohexanediol and 1,4-cyclohexanedimethanol.
[0326] Examples of the polycarbonate polyol include poly(hexamethylene carbonate) polyol obtained by a condensation reaction of 1,6-hexanediol and diethyl carbonate, poly(pentylene carbonate) obtained by a condensation reaction of pentanediol and diethyl carbonate, and poly(butylene carbonate) obtained by a condensation reaction of 1,4-butanediol and diethyl carbonate.
[0327] Commercially available polycarbonate polyols include PLACCEL CD CD205, PLACCEL CD CD210, PLACCEL CD CD220 (all manufactured by Daicel, trade names), DURANOL T5651, DURANOL T5652, DURANOL T5650J (all manufactured by Asahi Kasei Corporation, trade names), and the like.
[0328] (Molecular weight of polyol)
[0329] The molecular weight of the polyol described above is preferably 100 to 50,000, more preferably 150 to 10,000, and further preferably 150 to 5,000, in terms of number average molecular weight. If the number average molecular weight is too small, the crosslinking density increases, so the hardness of the matrix resin becomes too high, and the recording speed may decrease. In addition, if the number average molecular weight is too large, the compatibility with other components decreases, the crosslinking density decreases, and the hardness of the matrix resin becomes too low, and the recorded content may disappear.
[0330] <Other ingredients>
[0331] The matrix resin in the present embodiment may contain other components in addition to the above-mentioned components unless it violates the spirit of the present invention.
[0332] As such other components, for example, compounds having hydroxyl groups such as ethylene glycol, propylene glycol, 1,4-butanediol, 1,5-pentanediol, 3-methyl-1,5-pentanediol, 1,6-hexanediol, neopentyl glycol, diethylene glycol, 1,4-cyclohexanediol, 1,4-cyclohexanedimethanol, decanediol, trimethylolpropane, polyethylene glycol, and polytetramethylene glycol, which are used for the purpose of changing the physical properties of the matrix resin, can be cited.
[0333] <Urethane Polymerization Catalyst>
[0334] In order to promote the reaction of isocyanate and polyol, a suitable urethane polymerization catalyst may be included.
[0335] Examples of the urethane polymerization catalyst include onium salts such as bis(4-tert-butylphenyl)iodonium perfluoro-1-butanesulfonic acid, bis(4-tert-butylphenyl)iodonium p-toluenesulfonic acid, bis(4-tert-butylphenyl)iodonium trifluoromethanesulfonic acid, (4-bromophenyl)diphenylphosphonium trifluoromethanesulfonate, (4-tert-butylphenyl)diphenylsulfonium trifluoromethanesulfonic acid, diphenyliodonium perfluoro-1-butanesulfonic acid, (4-fluorophenyl)diphenylsulfonium trifluoromethanesulfonic acid, diphenyl-4-methylphenylsulfonium trifluoromethanesulfonic acid, triphenylsulfonium trifluoromethanesulfonic acid, and bis(alkylphenyl)iodonium hexafluorophosphonic acid, and Lewis acid such as zinc chloride, tin chloride, ferric chloride, aluminum chloride, BF3, etc. Catalysts containing an acid as a main component, protonic acids such as hydrochloric acid and phosphoric acid, amines such as trimethylamine, triethylamine, triethylenediamine, dimethylbenzylamine, and diazabicycloundecene, imidazoles such as 2-methylimidazole, 2-ethyl-4-methylimidazole, and 1-cyanoethyl-2-undecylimidazolinium trimellitate, bases such as sodium hydroxide, potassium hydroxide, and potassium carbonate, tin catalysts such as dibutyltin dilaurate, dioctyltin dilaurate, and dibutyltin dioctoate, bismuth catalysts such as tri(2-ethylhexanoate)bismuth and tribenzoyloxybismuth, zirconium catalysts such as tetrakis(ethyl acetoacetate), 1,1'-isopropylidene zirconocene dichloride, and tetrakis(2,4-pentanedione)zirconium, and the like.
[0336] Among them, bismuth catalysts and zirconium catalysts are preferred in order to improve storage stability.
[0337] The bismuth-based catalyst is not particularly limited as long as it is a catalyst containing a bismuth element and is a compound that promotes the reaction between isocyanate and polyol.
[0338] Examples of bismuth-based catalysts include bismuth tris(2-ethylhexanoate), tribenzoyloxybismuth, bismuth triacetate, bismuth tris(dimethyldithiocarbamate), bismuth hydroxide, triphenylbismuth(V)bis(trichloroacetate), tris(4-methylphenyl)oxybismuth(V), and triphenylbis(3-chlorobenzoyloxy)bismuth(V).
[0339] Among them, from the perspective of catalytic activity, trivalent bismuth compounds are preferred, and bismuth carboxylates and substances represented by the general formula Bi(OCOR)3 (R is a linear or branched alkyl, cycloalkyl, or substituted or unsubstituted aromatic group) are more preferred. The above-mentioned bismuth-based catalysts can be used alone or in any combination and ratio.
[0340] The zirconium-based catalyst is not particularly limited as long as it is a catalyst containing a zirconium element and is a compound that promotes the reaction between isocyanate and polyol.
[0341] Examples thereof include cyclopentadienyl zirconium trichloride, decamethyl zirconocene dichloride, 1,1'-dibutyl zirconocene dichloride, 1,1'-isopropyl zirconocene dichloride, tetrakis(2,4-pentanedione)zirconium, tetrakis(trifluoro-2,4-pentanedione)zirconium, tetrakis(hexafluoro-2,4-pentanedione)zirconium, zirconium butoxide, zirconium tert-butoxide, zirconium propoxide, zirconium isopropoxide, zirconium ethoxide, zirconium bis(ethyl acetoacetate)dibutoxide, zirconium tetrakis(ethyl acetoacetate), zirconium oxide, barium zirconium oxide, calcium oxide, zirconium bromide, zirconium chloride, zirconium fluoride, di(indenyl)zirconium dichloride, and zirconium carbonate.
[0342] Among them, compounds having an organic ligand are preferred from the perspective of compatibility with other components, and compounds having an alkoxide or acetylacetonate (2,4-pentanedione) structure are more preferred. The above zirconium compounds may be used alone or in any combination and ratio.
[0343] The bismuth-based catalyst and the zirconium-based catalyst may be used alone or in combination.
[0344] The amount of the urethane polymerization catalyst used is preferably usually 0.0001% by mass or more, especially 0.001% by mass or more, and usually 10% by mass or less, especially 5% by mass or less, based on the ratio to the base resin. If the amount of the urethane polymerization catalyst used is too small, curing may take too much time. On the other hand, if the amount is too large, control of the curing reaction may become difficult.
[0345] By using a urethane polymerization catalyst, curing can be performed at room temperature, but curing can also be performed at a higher temperature. The temperature at this time is preferably between 40°C and 90°C.
[0346] 6-1-3. Photocurable resin
[0347] When a photocurable resin is used as the matrix resin, it is necessary to use a matrix resin photoinitiator corresponding to the wavelength used for curing. Since curing during light irradiation may cause problems in molding and bonding, it is preferred to perform a stable curing reaction at the main operating temperature, that is, near room temperature. Considering this aspect, it can be said that catalyst curing based on a matrix resin photoinitiator is a preferred option.
[0348] It is common that active matrices such as cations or anions are generated from a photoinitiator for a matrix resin by light irradiation, and it is therefore considered preferable to select a substance that can be cured by these active matrices and cure it to form a matrix resin.
[0349] Examples of the functional group that reacts with cations such as protons include epoxy groups and oxetanyl groups. Examples of compounds having these functional groups include, specifically, polyglycidyl ether compounds of polyhydric alcohols such as (poly)ethylene glycol, (poly)propylene glycol, (poly)tetramethylene glycol, trimethylolpropane, and glycerol, alicyclic epoxy compounds having 4- to 7-membered cyclic aliphatic groups such as 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexylcarboxylate and 3,4-epoxy-1-methylcyclohexyl-3,4-epoxy-1-methylhexylcarboxylate, bisphenol A type epoxy compounds, hydrogenated bisphenol A type epoxy compounds, bisphenol F type epoxy compounds, and phenol or cresol novolac type epoxy compounds. Examples of compounds having an oxetane group include 2-ethyl-2-oxetane ether of bisphenol A and 1,6-bis(2-ethyl-2-oxetaneoxy)hexane. (It should be noted that "(poly)ethylene glycol" and the like herein refer to both "ethylene glycol" and "polyethylene glycol" which is a polymer thereof.)
[0350] Examples of the functional group that reacts with anions include epoxy groups and episulfide groups. Specific examples of compounds having an episulfide group include phenyl episulfide and diepithiosulfide methyl ether of bisphenol A.
[0351] The amount of the matrix resin photoinitiator used when photocuring the matrix resin is preferably usually 0.01% by mass or more, especially 0.1% by mass or more, and usually 1% by mass or less, especially 0.5% by mass or less, in terms of the ratio to the polymerizable compound. If the amount of the matrix resin photoinitiator is too small, curing may take too long. On the other hand, if the amount is too large, it may be difficult to control the curing reaction.
[0352] In addition, especially when used as a holographic recording material, since light irradiation is also performed during recording, it is important that the wavelength during curing is different from the wavelength during recording, and the difference in wavelength is at least 10 nm, preferably 30 nm. The selection of the photoinitiator for the matrix resin can be roughly predicted based on the absorption wavelength of the initiator.
[0353] 6-2. Photopolymerization initiator
[0354] As for the photopolymerization initiator assisting the polymerization of the compound of the present invention, any one can be used as long as it is a known photo-radical polymerization initiator. As an example, azo compounds, azide compounds, organic peroxides, organic borates, onium salts, bisimidazole derivatives, cyclopentadienyl titanium compounds, iodonium salts, organic thiol compounds, halogenated hydrocarbon derivatives, acetophenones, benzophenones, hydroxybenzenes, thioxanthones, anthraquinones, ketals, acylphosphine oxides, sulfone compounds, carbamic acid derivatives, sulfonamides, triarylcarbinols, oxime esters, etc. are used. Among them, as the photopolymerization initiator, cyclopentadienyl titanium compounds, acylphosphine oxide compounds, oxime ester compounds, etc. are preferred for the reason that polymerization reaction occurs under the action of light in the visible region.
[0355] 6-2-1. Cyclopentadienyl titanium compounds
[0356] When a cyclopentadienyl titanium compound is used as the photopolymerization initiator, the type thereof is not particularly limited, and for example, a cyclopentadienyl titanium compound can be appropriately selected from various cyclopentadienyl titanium compounds described in JP-A Nos. 59-152396 and 61-151197 and used.
[0357] Specific examples of cyclopentadienyl titanium compounds include biscyclopentadienyl-dichlorotitanium, biscyclopentadienyl-diphenyltitanium, biscyclopentadienyl-bis-2,3,4,5,6-pentafluorophenyl-1-yltitanium, biscyclopentadienyl-bis-2,3,5,6-tetrafluorophenyl-1-yltitanium, biscyclopentadienyl-bis-2,4,6-trifluorophenyl-1-yltitanium, biscyclopentadienyl-bis-2,6-di-fluorophenyl-1-yltitanium. i. biscyclopentadienyl-bis-2,4-di-fluorophenyl-1-yl Ti, bismethylcyclopentadienyl-bis-2,3,4,5,6-pentafluorophenyl-1-yl Ti, bismethylcyclopentadienyl-bis-2,3,5,6-tetrafluorophenyl-1-yl Ti, bismethylcyclopentadienyl-bis-2,6-difluorophenyl-1-yl Ti, biscyclopentadienyl-bis-2,6-difluoro-3-(pyrrol-1-yl)-phenyl-1-yl Ti, etc.
[0358] 6-2-2. Acylphosphine oxide compounds
[0359] Specific examples of the acylphosphine oxide compound include a monofunctional initiator having only one photo-cleavage site in one molecule and a bifunctional initiator having two photo-cleavage sites in one molecule.
[0360] Examples of the monofunctional initiator include triphenylphosphine oxide, diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide, and 2,6-dichlorobenzoyldiphenylphosphine oxide.
[0361] Examples of the bifunctional initiator include phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide, bis(2,6-dimethoxybenzoyl)-2,4,4-trimethylpentylphosphine oxide, bis(2,6-dichlorobenzoyl)-4-propylphenylphosphine oxide, and bis(2,6-dichlorobenzoyl)-2,5-dimethylphenylphosphine oxide.
[0362] 6-2-3. Oxime ester compounds
[0363] Specific examples of oxime ester compounds include 1-[4-(phenylthio)-2-(O-benzoyloxime)]-1,2-octanedione, 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]-1-(O-acetyloxime)ethanone, 4-(acetoxyimino)-5-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]-1-(O-acetyloxime)ethanone, 1-(9-ethyl-6-cyclohexanoyl-9H-carbazol-3-yl)-1-(O-acetyloxime)glutaric acid methyl ester, 1-(9-ethyl-9H-carbazol-3-yl)-1-(O-acetyloxime)glutaric acid methyl ester, 1-(9-ethyl-9H-carbazol-3-yl)-1-(O-acetyloxime)glutaric acid methyl ester, 1-(9-ethyl-9H-carbazol-3-yl)-1-(O-acetyloxime)-3-methyl-butyric acid, etc.
[0364] 6-2-4. Amount of photopolymerization initiator used
[0365] The above-mentioned various photopolymerization initiators may be used alone or in combination of two or more in any ratio.
[0366] The content of the photopolymerization initiator in the polymerizable composition of the present invention is preferably 0.5 μmol / g or more in terms of molar amount per unit weight of the polymerizable composition. More preferably, it is 1 μmol / g or more. In addition, the content of the photopolymerization initiator in the polymerizable composition of the present invention is preferably 100 μmol / g or less in terms of molar amount per unit weight of the polymerizable composition. More preferably, it is 50 μmol / g or less.
[0367] If the content of the photopolymerization initiator is too low, the amount of free radicals generated decreases, thereby slowing down the speed of photopolymerization and reducing the recording sensitivity in the holographic recording medium. On the other hand, if the content of the photopolymerization initiator is too high, the free radicals generated by light irradiation recombine with each other and disproportionate, thereby reducing the contribution to photopolymerization and still reducing the recording sensitivity in the holographic recording medium. When two or more photopolymerization initiators are used in combination, it is preferred that the total amount thereof satisfy the above range.
[0368] 6-3. Free radical scavengers
[0369] In holographic recording, in order to accurately fix the interference light intensity pattern in the form of polymer distribution in the holographic recording medium, a free radical scavenger can be added. The free radical scavenger preferably has both a functional group for capturing free radicals and a reactive group fixed to the matrix resin by covalent bonding. As the functional group for capturing free radicals, stable nitroxide free radicals can be cited.
[0370] 6-3-1. Types of free radical scavengers
[0371] Examples of the reactive group that can be fixed to the matrix resin by covalent bonding include hydroxyl, amino, isocyanate, and mercapto. Examples of such radical scavengers include 4-hydroxy-2,2,6,6-tetramethylpiperidin-1-oxyl radical (TEMPOL), 3-hydroxy-9-azabicyclo[3.3.1]nonane N-oxyl, 5-HO-AZADO: 5-hydroxy-2-azatricyclo[3.3.1.1 3,7 ]Decane N-oxyl.
[0372] 6-3-2. Content of free radical scavenger
[0373] The above-mentioned various free radical scavengers may be used alone or in combination of two or more in any ratio.
[0374] The content of the radical scavenger in the polymerizable composition of the present invention is preferably 0.5 μmol / g or more, more preferably 1 μmol / g or more, in terms of molar amount per unit weight of the polymerizable composition. In addition, the content of the radical scavenger in the polymerizable composition of the present invention is preferably 100 μmol / g or less, more preferably 50 μmol / g or less.
[0375] If the content of the radical scavenger is too little, the efficiency of catching free radicals decreases, and there is a tendency that the polymer with low polymerization degree diffuses and the components that do not contribute to the signal increase. On the other hand, if the content of the radical scavenger is too much, the polymerization efficiency of the polymer decreases, and there is a tendency that the signal recording cannot be performed. When two or more radical scavengers are used together, it is preferred that their total amount satisfy the above-mentioned range.
[0376] 6-4. Other ingredients
[0377] The polymerizable composition of the present invention may contain other components in addition to the above-mentioned components unless it violates the gist of the present invention.
[0378] As other components, solvents, plasticizers, dispersants, leveling agents, defoamers, adhesion promoters, etc. used to prepare polymerizable compositions can be cited, and in the case of holographic recording media in particular, chain transfer agents, polymerization terminators, compatibilizers, reaction adjuvants, sensitizers, etc. used to control the recording reaction can be cited. In addition, examples of additives that may be required to improve other properties can be cited as preservatives, stabilizers, antioxidants, ultraviolet absorbers, etc. These components can be used alone or in any combination and ratio.
[0379] <Sensitizer>
[0380] The polymerizable composition of the present invention may contain a compound that controls the excitation of the photopolymerization initiator. Examples of such a compound include a sensitizer and a sensitization auxiliary.
[0381] As a sensitizer, any sensitizer can be selected from known various sensitizers for use. Usually, as a sensitizer, in order to absorb visible and ultraviolet lasers, colored compounds such as pigments are used in most cases. In the case of a holographic recording medium, although it is different according to the wavelength of the laser used in the recording and the type of the initiator used, in the case of a system using a green laser, as a specific example of a preferred sensitizer, compounds recorded in Japanese Patent Laid-Open No. 5-241338, Japanese Patent Laid-Open No. 2-69, Japanese Patent Laid-Open No. 2-55446, etc. can be cited. In the case of a system using a blue laser, compounds recorded in Japanese Patent Laid-Open No. 2000-10277, Japanese Patent Laid-Open No. 2004-198446, etc. can be cited. These sensitizers can be used alone, or two or more can be used in any combination and ratio.
[0382] When the obtained holographic recording medium is required to be colorless and transparent, it is preferable to use a cyanine pigment as a sensitizer. Cyanine pigments are generally easily decomposed by the action of light, so by post-exposure, that is, by leaving the holographic recording medium under room light or sunlight for several hours to several days, the cyanine pigment in the holographic recording medium is decomposed and has no absorption in the visible region, so that a colorless and transparent holographic recording medium can be obtained.
[0383] The amount of the sensitizer needs to be increased or decreased according to the thickness of the recording layer to be formed, and is preferably generally 0.01% by mass or more, especially 0.1% by mass or more, and generally 10% by mass or less, especially 5% by mass or less, in terms of the ratio relative to the above-mentioned 6-2. photopolymerization initiator. If the amount of the sensitizer is too small, the initiation efficiency is reduced, and recording may take a long time. On the other hand, if the amount of the sensitizer is too much, the absorption of the light used in recording and regeneration increases, and the light may be difficult to reach the depth direction. When two or more sensitizers are used in combination, their total amount is made to meet the above range.
[0384] <Plasticizer>
[0385] The polymerizable composition of the present invention may contain a plasticizer in order to improve reaction efficiency and adjust the physical properties of the recording layer of the holographic recording medium.
[0386] Examples of plasticizers include phthalates such as dioctyl phthalate, diisononyl phthalate, diisodecyl phthalate, and diundecyl phthalate, adipates such as bis(2-ethylhexyl) adipate, diisononyl adipate, and di-n-butyl adipate, sebacic acid esters such as dioctyl sebacate and dibutyl sebacate, phosphates such as tricresyl phosphate, citrates such as acetyl tributyl citrate, trimellitic acid esters such as trioctyl trimellitic acid, epoxidized soybean oil, chlorinated paraffins, alkoxylated (poly) alkylene glycol esters such as acetoxymethoxypropane, and terminal alkoxylated polyalkylene glycols such as dimethoxypolyethylene glycol.
[0387] A plasticizer containing fluorine element as exemplified in Japanese Patent No. 6069294 may also be used. Examples of the plasticizer containing fluorine element include 2,2,2-trifluoroethyl butyl carbamate, bis(2,2,2-trifluoroethyl)-(2,2,4-trimethylhexane-1,6-diyl)biscarbamate, bis(2,2,2-trifluoroethyl)-[4-({[(2,2,2-trifluoroethoxy)carbonyl]amino}-methyl)octane-1,8-diyl]biscarbamate, 2,2,3,3,4,4,5,5,6,6,7,7,8,8,9,9-hexadecanoylbutylcarbamate, and 2,2,2-trifluoroethylphenylcarbamate.
[0388] These plasticizers are used in a range of usually 0.01% by mass to 50% by mass, preferably 0.05% by mass to 20% by mass, based on the total solid content of the polymerizable composition. If the content of the plasticizer is less than this ratio, the reaction efficiency will not be improved or the physical properties will not be adjusted; if it is more than this ratio, the transparency of the recording layer will decrease and the plasticizer will ooze out significantly.
[0389] <Leveling agent>
[0390] The polymerizable composition of the present invention may be used with a leveling agent. Examples of the leveling agent include polycarboxylic acid sodium salts, polycarboxylic acid ammonium salts, polycarboxylic acid amine salts, silicone leveling agents, acrylic leveling agents, ester compounds, ketone compounds, fluorine compounds, and the like. Any one of these may be used alone, or two or more may be used in any combination and ratio.
[0391] <Chain transfer agent>
[0392] The polymerizable composition of the present invention may be used with a chain transfer agent. Examples of the chain transfer agent include phosphites such as sodium phosphite and sodium hypophosphite, thiols such as mercaptoacetic acid, mercaptopropionic acid, 2-propanethiol, 2-mercaptoethanol, and thiophenol, aldehydes such as acetaldehyde and propionaldehyde, ketones such as acetone and methyl ethyl ketone, halogenated hydrocarbons such as trichloroethylene and perchloroethylene, terpenes such as terpinolene, α-terpinene, β-terpinene, and γ-terpinene, 1,4-cyclohexadiene, 1,4-cycloheptadiene, 1,4-cyclooctadiene, 1,4-heptadiene, 1,4-hexadiene, 2- Non-conjugated dienes such as methyl-1,4-pentadiene, 3,6-nonanedien-1-ol, and 9,12-octadecadienol, linolenic acid, γ-linolenic acid, linolenic acid methyl, linolenic acid ethyl ester, linolenic acid isopropyl, and linolenic anhydride, linoleic acid, linoleic acid methyl ester, linoleic acid ethyl ester, linoleic acid isopropyl, and linoleic anhydride, eicosapentaenoic acid, eicosapentaenoic acid ethyl ester, and other eicosapentaenoic acids, docosahexaenoic acid, docosahexaenoic acid ethyl ester, and other docosahexaenoic acids, and the like.
[0393] The amount of these additives used is preferably usually 0.001% by mass or more, especially 0.01% by mass or more, and usually 30% by mass or less, especially 10% by mass or less, in terms of the ratio to the total solid content of the polymerizable composition of the present embodiment. When two or more additives are used in combination, their total amount is adjusted to meet the above range.
[0394] 6-5. Composition ratio of each component in the polymerizable composition
[0395] The content of each component in the polymerizable composition of the present invention is arbitrary unless it violates the gist of the present invention. The ratio of each component shown below is preferably in the following range based on the molar amount per unit mass of the polymerizable composition.
[0396] The content of the polymerizable compound including the compound of the present invention is preferably 5 μmol / g or more, more preferably 10 μmol / g or more, and further preferably 100 μmol / g or more. In addition, the content of the polymerizable compound is preferably 2000 μmol / g or less, more preferably 1000 μmol / g or less, and further preferably 500 μmol / g or less.
[0397] By making the content of the polymerizable compound above the above lower limit, sufficient diffraction efficiency can be obtained in the holographic recording medium; by making the content below the above upper limit, compatibility with the resin matrix in the recording layer can be ensured, and there is a tendency to keep the shrinkage of the recording layer due to recording at a low level.
[0398] When isocyanate and polyol are used as the base resin in the polymerizable composition of the present invention, their total content is usually 0.1% by mass or more, preferably 10% by mass or more, more preferably 35% by mass or more, and usually 99.9% by mass or less, preferably 99% by mass or less. When the content is equal to or more than the above lower limit, it is easy to form a recording layer.
[0399] In this case, the ratio of the number of isocyanate-reactive functional groups of the polyol to the number of isocyanate groups of the isocyanate is preferably 0.1 or more, more preferably 0.5 or more, and is usually 10.0 or less, preferably 2.0 or less. By making this ratio within the above range, the number of unreacted functional groups is small and the storage stability is improved.
[0400] In addition, the content of the urethane polymerization catalyst in the polymerizable composition is preferably determined in consideration of the reaction rate of the isocyanate and the polyol, and is preferably 5% by mass or less, more preferably 4% by mass or less, and further preferably 1% by mass or less. In addition, it is preferably used at 0.005% by mass or more.
[0401] The total amount of the components other than the above components may be 30% by mass or less, preferably 15% by mass or less, and more preferably 5% by mass or less.
[0402] 6-6. Method for producing polymerizable composition
[0403] In the present invention, the method for producing the polymerizable composition comprising the polymerizable compound, the matrix resin and the photopolymerization initiator is not particularly limited, and the order of mixing can be appropriately adjusted. In addition, when the polymerizable composition contains components other than those described above, the components can be mixed in any combination and order.
[0404] The polymerizable composition in the case of using isocyanate and polyol as the base resin can be obtained, for example, by the following method, but the present invention is not limited thereto.
[0405] A polymerizable compound, a photopolymerization initiator, and all components except isocyanate and a urethane polymerization catalyst are mixed to prepare a photoreactive composition (liquid A). An isocyanate and a urethane polymerization catalyst are mixed to prepare a liquid B.
[0406] Alternatively, all components except isocyanate may be mixed with the polymerizable compound and the photopolymerization initiator to prepare a photoreactive composition (liquid A).
[0407] Each mixed solution is preferably dehydrated and degassed. If the dehydration and degassing are insufficient, bubbles will be generated when the holographic recording medium is produced, and a uniform recording layer may not be obtained. During the dehydration and degassing, heating and decompression may be performed as long as the components are not damaged.
[0408] The preparation of the polymerizable composition obtained by mixing liquid A and liquid B is preferably carried out immediately before the holographic recording medium is formed. At this time, a mixing technique based on an existing method can also be used. In addition, when liquid A and liquid B are mixed, degassing can be performed as needed to remove residual gas. In addition, liquid A and liquid B are preferably subjected to a filtering process in order to remove foreign matter and impurities separately or after mixing, and each liquid is more preferably filtered separately.
[0409] In addition, isocyanate functional prepolymers obtained by reacting isocyanate with polyols having excess isocyanate groups as isocyanates can also be used as matrix resins. In addition, isocyanate reactive prepolymers obtained by reacting polyols having excess isocyanate reactive functional groups as polyols with isocyanates can also be used as matrix resins.
[0410] 6-7. Holographic Recording Medium of the Present Invention
[0411] The holographic recording medium of the present invention using the polymerizable composition of the present invention has a recording layer, and further has a support and other layers as needed. Usually, the holographic recording medium has a support, and the recording layer and other layers are stacked on the support to constitute the holographic recording medium. However, when the recording layer or other layers have the strength and durability required by the medium, the holographic recording medium may not have a support. Examples of other layers include a protective layer, a reflective layer, an anti-reflective layer (anti-reflective film), etc.
[0412] 6-7-1. Recording layer
[0413] The recording layer of the holographic recording medium of the present invention is a layer formed of the polymerizable composition of the present invention, and is a layer for recording information. Information is usually recorded in the form of a hologram. As described in the recording method section described later, a part of the polymerizable compound (hereinafter referred to as a polymerizable monomer) contained in the recording layer undergoes chemical changes such as polymerization due to holographic recording, etc. Therefore, in the holographic recording medium after recording, a part of the polymerizable monomer is consumed and exists in the form of a reacted compound such as a polymer.
[0414] The thickness of the recording layer is not particularly limited and can be appropriately determined in consideration of the recording method, etc., and is preferably 1 μm or more, more preferably 10 μm or more, and preferably 1 cm or less, more preferably 3 mm or less. By making the thickness of the recording layer greater than the above lower limit, there is a tendency to improve the selectivity of each hologram when multiple recording is performed in the holographic recording medium and to improve the degree of multiple recording. By making the thickness of the recording layer less than the above upper limit, the entire recording layer can be uniformly formed, and there is a tendency to make the diffraction efficiency of each hologram uniform and perform multiple recording with a high S / N ratio.
[0415] From the viewpoint of recording and reproducibility, the shrinkage rate of the recording layer due to exposure during recording and reproduction of information is preferably 0.25% or less.
[0416] 6-7-2. Support
[0417] The support is not particularly limited in detail as long as it has the strength and durability required for the holographic recording medium, and any support can be used.
[0418] The shape of the support is not limited, but is usually formed in a flat plate shape or a film shape.
[0419] The material constituting the support is not limited either, and may be transparent or opaque.
[0420] As the material of the support, if transparent materials are mentioned, organic materials such as acrylic (acrylic), polyethylene terephthalate, polyethylene naphthalate, polycarbonate, polyethylene, polypropylene, amorphous polyolefin, polystyrene, polycycloolefin, cellulose acetate, etc. and inorganic materials such as glass, silicon, quartz, etc. are mentioned. Among them, polycarbonate, acrylic (acrylic), polyester, amorphous polyolefin, glass, etc. are preferred, and polycarbonate, acrylic (acrylic), amorphous polyolefin, polycycloolefin, glass are more preferred.
[0421] Examples of the material of the support include, if opaque materials, metals such as aluminum, and materials obtained by coating the above-mentioned transparent support with metals such as gold, silver, and aluminum, or dielectrics such as magnesium fluoride and zirconium oxide.
[0422] The thickness of the support is not particularly limited, and is preferably in the range of 0.05 mm to 1 mm. When the thickness of the support is above the lower limit, the mechanical strength of the holographic recording medium can be obtained, and the warping of the substrate can be prevented. When the thickness of the support is below the upper limit, the advantages of increasing the amount of light transmitted and reducing the weight and cost of the holographic recording medium can be obtained.
[0423] The surface of the support may be subjected to a surface treatment. This surface treatment is generally used to improve the adhesion between the support and the recording layer. Examples of surface treatments include subjecting the support to a corona discharge treatment or pre-forming an undercoat layer on the support. Compositions of the undercoat layer include halogenated phenols, or partially hydrolyzed vinyl chloride-vinyl acetate copolymers, polyurethane resins, and the like.
[0424] The surface treatment of the support may be performed for purposes other than improving adhesion. Examples thereof include reflective coating treatment for forming a reflective coating made of metals such as gold, silver, and aluminum; and dielectric coating treatment for forming a dielectric layer such as magnesium fluoride or zirconium oxide. These layers may be formed as a single layer or as two or more layers.
[0425] These surface treatments may also be performed for the purpose of controlling the gas or water permeability of the substrate. For example, by making the support sandwiching the recording layer also have the function of suppressing the gas or water permeability, the reliability of the holographic recording medium can be further improved.
[0426] The support may be provided only on one side of the upper side or the lower side of the recording layer of the holographic recording medium of the present invention, or may be provided on both sides. However, when the support is provided on both sides of the upper and lower sides of the recording layer, at least one of the supports is transparently constructed so as to transmit active energy rays (excitation light, reference light, regeneration light, etc.).
[0427] In the case of a holographic recording medium having a support on one or both sides of the recording layer, a transmissive or reflective hologram can be recorded. In the case of a support having a reflective property on one side of the recording layer, a reflective hologram can be recorded.
[0428] A pattern structure for data address may be provided on the support. There is no limitation on the patterning method in this case, for example, the support itself may be provided with a concavoconvex shape, a pattern may be formed on the reflective layer described later, or a combination of these methods may be used.
[0429] 6-7-3. Protective layer
[0430] The protective layer is a layer for preventing the recording and reproducing characteristics of the recording layer from being deteriorated. The specific composition of the protective layer is not limited, and any known composition can be applied. For example, a layer composed of a water-soluble polymer, an organic / inorganic material, etc. can be formed as the protective layer.
[0431] The position of the protective layer is not particularly limited, and it may be formed on the surface of the recording layer, between the recording layer and the support, or on the outer surface of the support. The protective layer may also be formed between the support and other layers.
[0432] 6-7-4. Reflection layer
[0433] The reflective layer is formed when the holographic recording medium is a reflective type. In the case of a reflective type holographic recording medium, the reflective layer may be formed between the support and the recording layer or on the outer side of the support, but is usually preferably located between the support and the recording layer.
[0434] As the reflective layer, any known reflective layer can be applied, and for example, a metal thin film or the like can be used.
[0435] 6-7-5. Anti-reflection film
[0436] For any type of holographic recording medium, whether transmissive or reflective, an anti-reflection film may be provided on the incident and outgoing sides of information light, reference light, and reproduction light, or between the recording layer and the support. The anti-reflection film improves the efficiency of light utilization and suppresses the generation of noise.
[0437] As the antireflection film, any known antireflection film can be used.
[0438] 6-7-6. Method for manufacturing holographic recording medium
[0439] There is no limitation on the method for producing the holographic recording medium of the present invention. For example, the polymerizable composition of the present invention can be coated on a support in the absence of a solvent to form a recording layer, thereby producing the holographic recording medium of the present invention. In this case, any coating method can be used. Specific examples include spraying, spin coating, wire rod coating, dipping, air knife coating, roll coating, blade coating, and scraper roll coating.
[0440] When forming a recording layer, especially when forming a thick recording layer, a method of placing it in a mold for molding or a method of applying it on a release film and pressing the mold can be adopted. Alternatively, the polymerizable composition of the present invention can be mixed with a solvent or an additive to prepare a coating liquid, which can be applied to a support and dried to form a recording layer for production. In this case, any method can be used as a coating method, for example, the same method as described above can be used.
[0441] The solvent used in the coating liquid is not limited. It is generally preferred to use a solvent that has sufficient solubility for the components used, can impart good film coating properties, and does not invade a support such as a resin substrate. The solvent can be used alone or in any combination and ratio. In addition, there is no restriction on the amount of the solvent. However, from the perspective of coating efficiency and handling properties, it is preferred to prepare a coating liquid with a solid content concentration of about 1 to 100% by mass.
[0442] Examples of solvents include ketone solvents such as acetone, methyl ethyl ketone, methyl isobutyl ketone, cyclohexanone, and methyl amyl ketone; aromatic solvents such as toluene and xylene; alcohol solvents such as methanol, ethanol, propanol, n-butanol, heptanol, hexanol, diacetone alcohol, and furfuryl alcohol; ketone alcohol solvents such as diacetone alcohol and 3-hydroxy-3-methyl-2-butanone; ether solvents such as tetrahydrofuran and dioxane; halogen solvents such as dichloromethane, dichloroethane, and chloroform; cellosolve solvents such as methyl cellosolve, ethyl cellosolve, butyl cellosolve, methyl cellosolve acetate, and ethyl cellosolve acetate; propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol monobutyl ether, propylene glycol monomethyl ether acetate, propylene glycol monoethyl ether acetate, and propylene glycol monobutyl ether. Ether acetate, dipropylene glycol dimethyl ether and other propylene glycol solvents; ethyl acetate, butyl acetate, amyl acetate, butyl acetate, ethylene glycol diacetate, diethyl oxalate, ethyl pyruvate, ethyl 2-hydroxybutyrate, ethyl acetoacetate, methyl lactate, ethyl lactate, methyl 2-hydroxyisobutyrate, methyl 3-methoxypropionate and other ester solvents; tetrafluoropropanol, octafluoropentanol, hexafluorobutanol and other perfluoroalkyl alcohol solvents; dimethylformamide, dimethylacetamide, N-methylpyrrolidone, dimethyl sulfoxide and other high polar solvents; n-hexane, n-octane and other chain hydrocarbon solvents; cyclohexane, methylcyclohexane, ethylcyclohexane, dimethylcyclohexane, n-butylcyclohexane, tert-butylcyclohexane, cyclooctane and other cyclic hydrocarbon solvents; or mixed solvents thereof, etc.
[0443] As methods for manufacturing holographic recording media, the following methods can also be cited, for example: a method in which a polymerizable composition melted under the action of heat is applied to a support, and the composition is cooled to solidify to form a recording layer; a method in which a liquid polymerizable composition is applied to a support, and the composition is thermally polymerized to solidify to form a recording layer; a method in which a liquid polymerizable composition is applied to a support, and the composition is photopolymerized to solidify to form a recording layer; and the like.
[0444] The holographic recording medium manufactured in this way can take the form of a self-standing plate or disk, and can be used in three-dimensional image display devices, diffractive optical elements, large-capacity storage devices, etc.
[0445] In particular, the holographic recording medium of the present invention using the polymerizable composition of the present invention has a high total Δn and is also useful as a light guide plate for AR glasses.
[0446] 6-7-7. Application of holographic recording media
[0447] <Mass storage usage>
[0448] Writing (recording) and reading (reproduction) of information on the holographic recording medium of the present invention are performed by irradiation with any light.
[0449] When recording information, light that can cause a chemical change in a polymerizable monomer, that is, light that causes its polymerization and concentration change, is used as object light (also referred to as recording light).
[0450] For example, in the case of recording information in the form of a volume hologram, the object light and the reference light are irradiated onto the recording layer together, and the object light and the reference light in the recording layer interfere with each other. As a result, the polymerization and concentration change of the polymerizable monomer in the recording layer are generated by the interference light. As a result, an interference fringe generates a refractive index difference in the recording layer, and is recorded in the recording layer in the form of a hologram by the interference fringe recorded in the above recording layer.
[0451] When regenerating the volume hologram recorded in the recording layer, a specific regeneration light (usually reference light) is irradiated onto the recording layer. The irradiated regeneration light diffracts corresponding to the above interference fringe. Since the diffracted light contains the same information as the above recording layer, the information recorded in the recording layer can be regenerated by reading the diffracted light using an appropriate detection means.
[0452] The wavelength regions of the object light, the regeneration light, and the reference light are arbitrary according to their respective uses, and can be in the visible light region or the ultraviolet region. Among these lights, as suitable lights, for example, solid-state lasers such as ruby, glass, Nd-YAG, Nd-YVO4, etc.; diode lasers such as GaAs, InGaAs, GaN, etc.; gas lasers such as helium-neon, argon, krypton, excimer, CO2, etc.; dye lasers having pigments, etc., lasers with excellent monochromaticity and directivity.
[0453] There is no limitation on the irradiation amounts of the object light, the regeneration light, and the reference light, and as long as they are within the range capable of recording and regeneration, their irradiation amounts are arbitrary. When the irradiation amount is extremely small, the chemical change of the polymerizable monomer is too incomplete, and there is a possibility that the heat resistance and mechanical properties of the recording layer cannot be fully exhibited; conversely, when the irradiation amount is extremely large, the components of the recording layer (the components of the polymerizable composition of the present invention) may deteriorate. Therefore, regarding the object light, the regeneration light, and the reference light, according to the composition of the polymerizable composition of the present invention used in the formation of the recording layer, the type and mixing amount of the photoinitiator, etc., it is usually irradiated in the range of 0.1 J / cm 2 above, 20 J / cm 2 below.
[0454] As holographic recording methods, there are a polarization coaxial holographic recording method, a reference light incident angle multiplex holographic recording method, etc. When using the holographic recording medium of the present invention as a recording medium, good recording quality can be provided by using any recording method.
[0455] <AR glasses light guide plate use>
[0456] In the holographic recording medium of the present invention, a volume hologram is recorded in the same manner as in the above-mentioned mass storage application.
[0457] For the volume hologram recorded on the recording layer, a specific regeneration light is irradiated to the recording layer. The irradiated regeneration light diffracts corresponding to the above-mentioned interference fringes. At this time, even if the wavelength of the regeneration light is inconsistent with the wavelength of the recording light, diffraction occurs as long as the above-mentioned interference fringes and Bragg conditions are met. Therefore, if the corresponding interference fringes are recorded according to the wavelength and incident angle of the regeneration light that is desired to be diffracted, diffraction can occur for the regeneration light in a wide wavelength region, which can expand the display color gamut of the AR glasses.
[0458] If the corresponding interference fringes are recorded according to the wavelength and diffraction angle of the regenerated light, the regenerated light incident from the outside of the holographic recording medium can be guided into the inside of the holographic recording medium, or the regenerated light guided into the inside of the holographic recording medium can be reflected, split, enlarged, or reduced, or the regenerated light guided into the inside of the holographic recording medium can be emitted to the outside of the holographic recording medium, thereby expanding the viewing angle of the AR glasses.
[0459] The wavelength region of the object light and the regeneration light is arbitrary according to their respective uses, and can be the visible light region or the ultraviolet region. Among these lights, as suitable light, the above-mentioned laser can be cited. As the regeneration light, it is not limited to lasers, etc., and display devices such as liquid crystal display (LCD) or organic electroluminescent display (OLED) can also be cited as suitable devices.
[0460] There is no limitation on the irradiation amount of the object light, the regeneration light, and the reference light. As long as it is within the range that can record and reproduce, the irradiation amount is arbitrary. When the irradiation amount is too small, the chemical change of the polymerizable monomer is too incomplete, and there is a possibility that the heat resistance and mechanical properties of the recording layer cannot be fully manifested; on the contrary, when the irradiation amount is too large, the components of the recording layer (components of the polymerizable composition of the present invention) may deteriorate. Therefore, regarding the object light, the regeneration light, and the reference light, the irradiation amount is usually 0.1 J / cm2, depending on the composition of the polymerizable composition of the present invention used in the formation of the recording layer, the type and mixing amount of the photopolymerization initiator, etc. 2 Above, 20J / cm 2 The following ranges are irradiated.
[0461] 6-8. Performance indicators of holographic recording media
[0462] The performance of the holographic recording medium is measured by the total sum of the diffraction efficiencies in the multiple recordings, totalΔn. In the case of a transmission hologram, the diffraction efficiency of the hologram is given as the ratio of the diffracted light intensity to the sum of the transmitted light intensity and the diffracted light intensity. Based on the obtained diffraction efficiency, Δn is calculated using the following formula based on Coupled Wave Theory (H. Kogelnik, The Bell System Technical Journal (1969), 48, 2909-2947), and the total sum in the multiple recordings is taken as totalΔn.
[0463] [Number 1]
[0464]
[0465] totalΔn=∑Δn
[0466] Here η is the diffraction efficiency, T is the thickness of the medium, λ is the wavelength of the reference light, and θ is the incident angle of the reference light.
[0467] In the case of large-capacity storage, the higher the totalΔn, the more information can be recorded per unit volume, which is preferable. In addition, in the case of AR glasses, the higher the totalΔn, the brighter the projector image can be transmitted to the eyes, the lower the power consumption, and the wider the viewing angle, which is preferable.
[0468] Example
[0469] The present invention is described in more detail below by way of examples. The present invention is not limited to the following examples unless the gist thereof is exceeded.
[0470] Hereinafter, the synthesis method will be described in detail with the chemical formula including the synthesis process attached to each compound.
[0471] [Raw materials used]
[0472] The composition raw materials used in Examples and Comparative Examples are as follows.
[0473] <Isocyanate>
[0474] DURANATE (registered trademark) TSS-100: Hexamethylene diisocyanate-based polyisocyanate (NCO 17.6%) (manufactured by Asahi Kasei Corporation)
[0475] <Polyol>
[0476] PLACCEL PCL-205U: polycaprolactone diol (molecular weight 530) (manufactured by Daicel)
[0477] PLACCEL PCL-305: Polycaprolactone triol (molecular weight 550) (manufactured by Daicel)
[0478] <Photopolymerization Initiator>
[0479] HLI02: 1-(9-ethyl-6-cyclohexanoyl-9H-carbazole-3-yl)-1-(O-acetyloxime)glutaric acid methyl ester
[0480] <Free Radical Scavenger>
[0481] TEMPOL: 4-Hydroxy-2,2,6,6-tetramethylpiperidin-1-oxyl radical (manufactured by Tokyo Chemical Industry Co., Ltd.)
[0482] <Urethane Polymerization Catalyst>
[0483] Bismuth tris(2-ethylhexanoate)octanoate solution (active ingredient content 56% by mass)
[0484] (Synthesis example 1)
[0485] Bis(4-dibenzothiophenyl)disulfide (DBTDS) as compound S-1 and 4-dibenzothiophenethiol (DBTSH) as compound S-2 were produced by the following synthesis method using the method described in JP-A-2017-14213.
[0486] [Chemistry 16]
[0487]
[0488] 20 g of dibenzothiophene was dissolved in 300 mL of THF, and 74.6 mL of a 1.6 M n-butyl lithium hexane solution was added while cooling to 0°C, and the mixture was heated to 20°C and stirred for 2 hours. The resulting brown reaction solution was cooled to -40°C, and 3.8 g of sulfur (powdered, manufactured by Wako Pure Chemical Industries, Ltd.) was added. After stirring at -40°C for 30 minutes, 5 mL of water was added to the reaction solution to stop the reaction.
[0489] The obtained solution was concentrated with an evaporator, and the obtained solid was washed with 100 mL of toluene for 30 minutes, and the yellow solid was filtered off to prepare DBTDS as compound S-1.
[0490] After dispersing compound S-1 in 200 mL of THF, 4.5 g of sodium borohydride was added and stirred at 50° C. for 1 hour. The reaction solution was then filtered, the resulting solution was concentrated using an evaporator, and 200 mL of toluene was added. The toluene solution was washed with water, 1 N hydrochloric acid, and 1 N aqueous sodium hydroxide solution, and the solution was concentrated. Recrystallization was performed using hexane to obtain 9.4 g (40% yield) of DBTSH as compound S-2.
[0491] Add several milliliters of deuterated chloroform to an appropriate amount (about 10 mg) of the obtained compound S-2 to dissolve it, and if there is an insoluble component, filter it with a cotton plug, transfer the solution to a special sample tube and cover it. Using this solution, a 400MHz nuclear magnetic resonance device (NMR) is used to measure the resonance state of hydrogen, so that each resonance line is attributed to the hydrogen of the compound, and it is confirmed that the target object has been obtained. The measurement data are shown below. For each target object described below, it is also measured in the same way to confirm that the target object has been obtained. The measurement data are shown below.
[0492] 1 HNMR (400MHz, CDCl3, δ, ppm) 3.63 (s, 1H), 7.35 (Ar, 1H), 7.45 (Ar, 3H), 7.89 (Ar, 1H), 8.05 (Ar, 1H), 8.14 (Ar, 1H)
[0493] (Synthesis example 2)
[0494] Bis[2-(2-benzothiazolyl)phenyl]disulfide (MPBTD) as compound S-3 was produced by the following synthesis method.
[0495] [Chemistry 17]
[0496]
[0497] 170 g of thiosalicylic acid and 165 g of 2-aminobenzenethiol were dissolved in 1.1 L of polyphosphoric acid, and the mixture was reacted at 170° C. for 2 hours. After cooling to below 100° C., the mixture was poured into 3 L of water and stirred vigorously. After stirring at room temperature for 2 hours, the solid matter was filtered out, and the obtained solid was poured into 3 L of saturated sodium bicarbonate aqueous solution and stirred for 20 minutes. After filtering out the solid matter, it was further poured into 3 L of water, suspended and washed, and filtered out to obtain 260 g of a crude product.
[0498] The above crude product 260g and sodium iodide 1.6g were dissolved in THF 5L, and 30% hydrogen peroxide 78mL was slowly added dropwise to the obtained mixture while keeping the internal temperature below 15°C. After stirring at 15°C for 15 minutes, the completion of the reaction was confirmed by LC analysis. Saturated sodium sulfite 500mL was slowly added to stop the reaction, and then 8L of water was added to dilute the mixture. After filtering out the generated solid matter, it was suspended and washed twice with 300mL of deionized water to obtain about 300g of crude product.
[0499] This was dissolved in THF and purified by silica gel chromatography to obtain 240 g of a light yellow solid, which was suspended and washed in 500 mL of THF, filtered, and washed twice with 20 mL of THF to obtain 220 g of MPBPD as compound S-3 as a white solid.
[0500] The NMR measurement data of compound S-3 are as follows.
[0501] 1 HNMR (400MHz, CDCl3, δ, ppm) 7.29 (td, 2H), 7.35 (td, 2H), 7.42 (td, 3H), 7.51 (td, 2H), 7.83 (dd, 2H), 7.90 (dd, 2H), 7.93 (dd, 2H), 8.13 (d, 2H)
[0502] (Example 1)
[0503] Compound M-1 was produced by the following synthesis method.
[0504] [Chemistry 18]
[0505]
[0506] The intermediate compound S-4 is prepared by two reaction routes (A) and (B).
[0507] Reaction route (A): Dissolve 20 g of DBTSH (compound S-2) obtained in Synthesis Example 1 and 50 g of cesium carbonate in 200 mL of methyl ethyl ketone (MEK). Add 9 g of pentaerythritol tribromide to the solution, raise the temperature to 90°C, and stir for 5 hours while confirming the progress of the reaction by LC analysis. After adding water to the reaction solution, add 100 mL of ethyl acetate to extract the organic layer. The obtained organic layer is extracted twice with 50 mL of water, and the generated aqueous layer is reverse-extracted twice with 100 mL of ethyl acetate. The obtained organic layer is dried with Glauber's salt and then concentrated. The crude product obtained by the above concentration is purified using a silica gel column (hexane-ethyl acetate) to obtain compound S-4: 10 g (49% yield).
[0508] Reaction route (B): 8.3 g of DBTDS (compound S-1) obtained in Synthesis Example 1, 3.5 g of pentaerythritol tribromide, 14 g of potassium carbonate, and 10 g of sodium formaldehyde sulfoxylate (rongalite) were suspended in 25 mL of N,N-dimethylformamide (DMF). The reaction mixture was heated to 100°C and stirred for 3 hours while confirming the reaction by LC analysis. After adding water to the reaction solution, 100 mL of ethyl acetate was added to extract the organic layer. The obtained organic layer was extracted twice with 60 mL of water, and the generated water layer was back-extracted twice with 70 mL of ethyl acetate. The obtained organic layer was dried with Glauber's salt and concentrated. The crude product obtained by the above concentration was suspended and washed with a mixed solvent of hexane: ethyl acetate 2:1 to obtain compound S-4: 4.8 g (61% yield).
[0509] The NMR measurement data of compound S-4 are as follows.
[0510] 1 HNMR (400MHz, CDCl3, δ, ppm) 3.38 (s, 6H), 3.75 (d, 2H), 7.22 (dd, 3H), 7.43 (Ar, 9H), 7.77 (Ar, 3H), 7.86 (dd, 3H), 8.02 (Ar, 3H)
[0511] The compound S-4 (11 g) obtained above was dissolved in 55 mL of tetrahydrofuran (THF), and 190 mg of dibutyltin dilaurate was added. 2.55 g of 2-isocyanatoethyl acrylate (produced by Showa Denko K.K., Karenz AOI) was added to the solution, and the reaction was carried out at room temperature. After 24 hours, 0.4 g of 2-isocyanatoethyl acrylate was added, and the reaction was further carried out for 24 hours. 100 mL of ethyl acetate was added to the reaction solution, and it was concentrated to about 50 mL. After removing the insoluble matter, the mixture was concentrated, and the obtained crude product was purified using a silica gel column (hexane-ethyl acetate) to obtain compound M-1: 7.6 g (58% yield).
[0512] The NMR measurement data of compound M-1 are as follows.
[0513] 1 HNMR (400MHz, CDCl3, δ, ppm) 3.19 (dt, 2H), 3.36 (s, 6H), 4.02 (m, 2H), 4.21 (s, 2H), 4.42 (m, 2H), 5.79 (dd, 1H), 6 .03(dd, 1H), 6.37(d, 1H), 7.19(Ar, 3H), 7.38(Ar, 3H), 7.43(Ar, 6H), 7.76(Ar, 3H), 7.84(Ar, 3H), 8.01(Ar, 3H)
[0514] <Production of Hologram Recording Medium 1>
[0515] Liquid A was prepared by dissolving 0.269 g of compound M-1 as a polymerizable monomer, 0.0097 g of a photopolymerization initiator HLI02, and 3.33 mg of a radical scavenger TEMPOL in 2.53 g of DURANATE (registered trademark) TSS-100.
[0516] Separately, 1.73 g of PLACCEL PCL-205U and 0.74 g of PLACCEL PCL-305 were mixed (PLACCEL PCL-205U:PLACCEL PCL-305=70:30 (mass ratio)), and 0.3 mg of an octanoic acid solution of bismuth tri(2-ethylhexanoate) was dissolved therein to prepare a liquid B.
[0517] After degassing each of liquid A and liquid B at 45° C. for 2 hours under reduced pressure, 2.39 g of liquid A and 2.11 g of liquid B were stirred and mixed, and further degassed under vacuum for several minutes.
[0518] Next, the vacuum degassed mixed solution was poured onto a glass slide having spacers of 0.5 mm thickness placed on two opposing end edges, a glass slide was placed thereon, the periphery was fixed with a clamp, and heated at 80° C. for 24 hours to produce a holographic recording medium 1 as an evaluation sample. The evaluation sample was formed by forming a recording layer of 0.5 mm thickness between the glass slides as covers.
[0519] The holographic recording medium 1 was mixed so that the ratio of the number of isocyanate groups in liquid A to the number of isocyanate reactive groups in liquid B was 1.0, and the polymerizable monomer was 58.3 μmol / g, the photopolymerization initiator was 3.63 μmol / g, and the radical scavenger was 3.63 μmol / g.
[0520] <Production of Hologram Recording Medium 2>
[0521] A liquid was prepared by dissolving 0.568 g of the compound M-1 as a polymerizable monomer, 0.0204 g of a photopolymerization initiator HLI02, and 7.04 mg of a radical scavenger TEMPOL in 2.62 g of DURANATE (registered trademark) TSS-100.
[0522] Separately, 1.19 g of PLACCEL PCL-205U and 1.19 g of PLACCEL PCL-305 were mixed (PLACCEL PCL-205U:PLACCEL PCL-305=50:50 (weight ratio)), and 0.3 mg of an octanoic acid solution of bismuth tri(2-ethylhexanoate) was dissolved therein to prepare a liquid B.
[0523] After degassing each of liquid A and liquid B at 45° C. for 2 hours under reduced pressure, 2.58 g of liquid A and 1.91 g of liquid B were stirred and mixed, and further degassed under vacuum for several minutes.
[0524] Next, the vacuum degassed mixed solution was poured onto a glass slide having spacers of 0.5 mm thickness placed on two opposing end edges, a glass slide was placed thereon, the periphery was fixed with a clamp, and heated at 80° C. for 24 hours to produce a holographic recording medium 2 as an evaluation sample. The evaluation sample was formed by forming a recording layer of 0.5 mm thickness between the glass slides as covers.
[0525] The holographic recording medium 2 was mixed so that the ratio of the number of isocyanate groups in liquid A to the number of isocyanate reactive groups in liquid B was 1.0, and the polymerizable monomer was 116 μmol / g, the photopolymerization initiator was 7.26 μmol / g, and the radical scavenger was 7.26 μmol / g.
[0526] [Holographic recording and evaluation method]
[0527] Using the hologram recording media 1 and 2 produced as evaluation samples, hologram recording and evaluation of the hologram recording performance of the hologram recording media were performed by the following procedure.
[0528] For holographic recording, a semiconductor laser with a wavelength of 405 nm was used and the exposure power density per beam was 7.5 mW / cm 2 use Figure 1 The exposure device shown performs holographic recording of a two-beam plane wave. The medium is rotated from -18° to 18°, and angle multiple recording is performed on the same position. The diffraction efficiency in each multiple recording is measured. Δn is calculated from the obtained diffraction efficiency, and the total of the multiple recording is taken as totalΔn.
[0529] The details are described below.
[0530] (Holographic Recording)
[0531] Figure 1 This is a diagram showing the outline of a device used for holographic recording.
[0532] Figure 1 In the figure, S is a sample of the holographic recording medium, M1 to M3 are all reflectors. PBS is a polarization beam splitter, and L1 is a laser source for recording light that emits light of wavelength 405 nm (TOPTICA Photonics single-mode laser that can produce light of wavelength near 405 nm). Figure 11 is a LED unit.
[0533] like Figure 1 As shown, light of wavelength 405 nm is split by a polarization beam splitter ("PBS" in the figure) and crosses on the recording surface in such a way that the angle formed by the two beams is 37.3°. At this time, irradiation is performed in such a way that the bisector of the angle formed by the two beams is perpendicular to the recording surface, and further, the vibration plane of the electric field vector of the two beams obtained by the beam splitting is perpendicular to the plane containing the two crossed beams.
[0534] After holographic recording, a He-Ne laser that can produce light at a wavelength of 633nm (V05-LHP151 manufactured by Melles Griot: "L2" in the figure) is used to irradiate the light at an angle of 30.0° relative to the recording surface, and the diffracted light is detected using a photodiode and a photoelectric sensor amplifier (S2281, C9329 manufactured by Hamamatsu Photonics: "PD1" in the figure) to determine whether the holographic recording has been performed correctly.
[0535] (Determination of diffraction efficiency)
[0536] For a sample that is moved at an angle relative to the optical axis (double beam, i.e. from Figure 1 The angle formed by the bisector of the inner angle at the point where the incident light of the reflectors M1 and M2 intersects and the normal line from the sample) was -18° to 18°, and 91 multiple recordings were performed at intervals of 0.4°, or 121 multiple recordings were performed at intervals of 0.3°.
[0537] After multiple recording, the LED unit (1 in the figure, central wavelength 405nm) is illuminated for a certain period of time to consume the remaining initiator and monomer. This process is called post-exposure. 2 , integrated energy is 12J / cm 2 Perform irradiation.
[0538] The diffraction efficiency of a hologram is given as the ratio of the diffracted light intensity to the sum of the transmitted light intensity and the diffracted light intensity. Figure 1 The light (wavelength 405nm) reflected by the reflector M1 in the image was measured to obtain the diffraction efficiency at angles from -19° to 19°. Based on the obtained diffraction efficiency, Δn was calculated using the following formula based on Coupled Wave Theory (H. Kogelnik, The Bell System Technical Journal (1969), 48, 2909-2947), and the total value in the multiple recording was taken as total Δn.
[0539] [Number 2]
[0540]
[0541] totalΔn=∑θn
[0542] Here, η is the diffraction efficiency, T is the thickness of the medium, λ is the wavelength of the reference light, and θ is the incident angle of the reference light (18.65°).
[0543] Using the prepared multiple samples, multiple evaluations were performed by changing the irradiation energy conditions such as increasing and decreasing the irradiation energy at the beginning of recording and increasing and decreasing the total irradiation energy, and the conditions under which the polymerizable monomer is almost exhausted (totalΔn reaches a rough balance in multiple recordings) were explored so that totalΔn reaches the maximum value. The maximum value obtained was taken as the totalΔn of the medium.
[0544] (Measurement of transmittance before recording and transmittance after recording)
[0545] The transmittance before recording was measured by measuring the ratio of the transmitted light power of the evaluation sample before recording to the incident light power.
[0546] The post-recording transmittance was measured by measuring the ratio of the transmitted light power to the incident light power of the evaluation sample that was post-exposed after hologram recording.
[0547] The hologram recording media 1 and 2 were evaluated by the above-mentioned method. The results are shown in Table 1 below.
[0548] (Example 2)
[0549] Compound M-2 was produced by the following synthesis method.
[0550] [Chemistry 19]
[0551]
[0552] 1.12 g of compound S-3 (MPBTD) obtained in Synthesis Example 2, 500 mg of pentaerythritol tribromide, 640 mg of potassium carbonate, and 820 mg of sodium formaldehyde sulfoxylate (rongalite) were suspended in 2.5 mL of N,N-dimethylformamide (DMF). The reaction mixture was heated to 80°C and stirred for 4 hours while confirming the progress of the reaction by LC analysis. Compound S-3 (190 mg) and 140 mg of rongalite were added and stirred at 80°C for 2 hours. After adding water to the reaction solution, 50 mL of ethyl acetate was added to extract the organic layer. The obtained organic layer was extracted twice with 30 mL of water, and the generated water layer was back-extracted twice with 50 mL of ethyl acetate. The obtained organic layer was dried with Glauber's salt and concentrated. The crude product obtained by the above concentration was purified using a silica gel column (hexane-ethyl acetate) to obtain compound S-5: 1.17 g (93% yield).
[0553] The NMR measurement data of compound S-5 are as follows.
[0554] 1 HNMR (400MHz, CDCl3, δ, ppm) 3.17 (s, 6H), 3.28 (t, 1H), 3.64 (d, 2H), 7.23 (Ar, 6H), 7.38 (Ar, 3H), 7.48 (Ar, 6H), 7.85 (Ar, 3H), 7.88 (Ar, 3H), 8.07 (Ar, 3H)
[0555] The compound S-5 (1.8 g) obtained above was dissolved in 9 mL of tetrahydrofuran (THF), and 28 mg of dibutyltin dilaurate was added. 375 mg of 2-isocyanatoethyl acrylate (produced by Showa Denko, Karenz AOI) was added to the solution, and the reaction was carried out at room temperature. After 24 hours, 375 mg of 2-isocyanatoethyl acrylate was added, and the reaction was further carried out for 24 hours. After adding 0.1M sodium hydroxide aqueous solution to the reaction solution, 50 mL of ethyl acetate was added to extract the organic layer. The obtained organic layer was extracted twice with 30 mL of water, and the generated aqueous layer was back-extracted twice with 50 mL of ethyl acetate. The obtained organic layer was dried with magnesium sulfate and concentrated below 25°C. The crude product obtained by the above concentration was purified using a silica gel column (hexane-ethyl acetate) to obtain compound M-2: 0.7 g (33% yield).
[0556] The NMR measurement data of compound M-2 are as follows.
[0557] 1HNMR (400MHz, CDCl3, δ, ppm) 3.27 (dt, 2H), 3.93 (s, 6H), 4.12 (t, 2H), 5.25 (t, 1H), 5.80 (dd, 1H), 6.10 (dd, 1H), 6.40 (d, 1H), 7.16 (Ar, 3H), 7.23 (Ar, 3H), 7.39 (Ar, 6H), 7.48 (Ar, 3H), 7.85 (Ar, 3H), 7.90 (Ar, 3H), 8.04 (Ar, 3H)
[0558] A hologram recording medium 1 was prepared and evaluated in the same manner as in Example 1 except that the compound M-2 was used as the polymerizable monomer. The results are shown in Table 1 below.
[0559] (Example 3)
[0560] Compound M-3 was produced by the following synthesis method.
[0561] [Chemistry 20]
[0562]
[0563] The compound S-4 (1.4 g) obtained in Example 1 was dissolved in 10 mL of tetrahydrofuran, and 22 mg of dibutyltin dilaurate was added. 550 mg of 1,1-(bisacryloyloxymethyl)ethyl isocyanate (Karenz BEI manufactured by Showa Denko Co., Ltd.) was added to the solution, and the reaction was carried out at room temperature. After 24 hours, 110 mg of 1,1-(bisacryloyloxymethyl)ethyl isocyanate was added, and the reaction was further carried out for 24 hours. After adding a saturated aqueous sodium carbonate solution to the reaction solution, 50 mL of ethyl acetate was added to extract the organic layer. The obtained organic layer was extracted twice with 50 mL of water, and the generated aqueous layer was reversely extracted twice with 50 mL of ethyl acetate. The obtained organic layer was dried with sodium sulfate and concentrated below 25°C. The crude product obtained by the above concentration was purified by a silica gel column (hexane-ethyl acetate), and then further purified by a reverse phase column to obtain compound M-3: 1.5 g (81% yield).
[0564] The NMR measurement data of compound M-3 are as follows.
[0565] 1HNMR (400MHz, CDCl3, δ, ppm) 1.23 (s, 3H), 3.39 (s, 6H), 4.09 (d, 2H), 4.20 (d, 2H), 4.22 (s, 2H), 4.63 (s, 1H), 5.76 (d, 2H), 6.02(dd, 2H), 6.35(d, 2H), 7.20(Ar, 3H), 7.39(Ar, 3H), 7.45(Ar, 6H), 7.77(Ar, 3H), 7.86(Ar, 3H), 8.03(Ar, 3H)
[0566] A hologram recording medium 2 was prepared and evaluated in the same manner as in Example 1 except that a mixture of Compound M-3 and Compound M-9 prepared in Comparative Example 9 described later was used as a polymerizable monomer (molar ratio 10 / 90).
[0567] (Example 4)
[0568] Compound M-4 was produced by the following synthesis method.
[0569] [Chemistry 21]
[0570]
[0571] The compound S-4 (3.0 g) obtained in Example 1 above and triethylamine (3.5 mL) were dissolved in 15 mL of dichloromethane. After the mixture was cooled to 0°C, 540 mg of bromoacetic acid bromide was slowly added dropwise. After stirring at room temperature for 1 hour, it was cooled to 0°C again, and 540 mg of bromoacetic acid bromide was added dropwise to the obtained reaction mixture. After stirring at room temperature for 1 hour, 20 mL of saturated sodium bicarbonate aqueous solution and 50 mL of ethyl acetate were added in sequence to perform extraction. The obtained organic layer was extracted twice with 50 mL of water, and the generated aqueous layer was back-extracted twice with 50 mL of ethyl acetate. The obtained organic layer was dried with Glauber's salt and concentrated to obtain 2.2 g of a crude product of compound S-6.
[0572] The crude product was dissolved in 11 mL of acetone and 1.6 mL of triethylamine was added. 500 mg of acrylic acid was slowly added to the mixture and stirred at room temperature for 1 hour. 500 mg of acrylic acid was added and stirred for another 1 hour. 20 mL of saturated aqueous sodium bicarbonate solution was added to the reaction mixture and extracted with 50 mL of dichloromethane. The aqueous layer was extracted again with 50 mL of dichloromethane and the obtained organic layer was washed with 60 mL of water. The organic layer was dried and concentrated with Glauber's salt and purified using a silica gel column (hexane-ethyl acetate) to obtain compound M-4: 440 mg (13% yield).
[0573] The NMR measurement data of compound M-4 are as follows.
[0574] 1 HNMR (400MHz, CDCl3, δ, ppm) 3.34 (s, 6H), 4.23 (s, 2H), 4.27 (s, 2H) 5.76 (dd, 1H), 6.00 (dd, 1H), 6 .32(d, 1H), 7.21(Ar, 3H), 7.39(Ar, 3H), 7.43(Ar, 6H), 7.76(Ar, 3H), 7.87(Ar, 3H), 8.01(Ar, 3H)
[0575] A hologram recording medium 1 was prepared and evaluated in the same manner as in Example 1 except that the compound M-4 was used as the polymerizable monomer. The results are shown in Table 1 below.
[0576] (Example 5)
[0577] Compound M-5 was produced by the following synthesis method.
[0578] [Chemistry 22]
[0579]
[0580] Suspend 13.60 g of 2-bromobenzenethiol, 7.08 g of pentaerythritol tribromide, and 9.04 g of potassium carbonate in 21 mL of N,N-dimethylformamide (DMF). Heat the reaction mixture to 100°C and stir for 4 hours while confirming the progress of the reaction by LC analysis. After cooling to room temperature, extract with ethyl acetate and wash with water. Reverse extract the aqueous layer with ethyl acetate twice. Dry the obtained organic layer with Glauber's salt and concentrate it. The crude product obtained by the above concentration is purified by silica gel column (hexane-ethyl acetate) to obtain compound S-7: 13.2 g (93% yield).
[0581] The NMR measurement data of compound S-7 are as follows.
[0582] 1 HNMR (400MHz, CDCl3, δ, ppm) 3.23 (s, 6H), 3.79 (d, 2H), 6.98 (Ar, 3H), 7.19 (Ar, 3H), 7.33 (Ar, 3H), 7.47 (Ar, 3H)
[0583] The compound S-7 (2.0 g) obtained above, 3.5 g of dibenzothiophene-4-boric acid, and 2.5 g of potassium carbonate were suspended in 20 mL of THF and 2.0 mL of water, and degassed by the circulation of nitrogen. 30 mg of dichlorobis[di-tert-butyl(p-dimethylaminophenyl)phosphine]palladium(II) was added to the reaction solution, and nitrogen was further passed for 10 minutes. The reaction solution was heated under a nitrogen atmosphere and stirred under reflux for 6 hours. After cooling to room temperature, it was extracted with ethyl acetate and washed with water. The aqueous layer was extracted twice with ethyl acetate, and 0.4 g of activated carbon was added to the obtained organic layer, and stirred for 30 minutes. After filtration with diatomaceous earth, it was concentrated, and the obtained crude product was purified using a silica gel column (hexane-ethyl acetate) to obtain compound S-8: 2.9 g (98% yield).
[0584] The NMR measurement data of compound S-8 are as follows.
[0585] 1 HNMR (400MHz, CDCl3, δ, ppm) 2.62 (s, 6H), 3.00 (d, 2H), 7.16 (Ar, 12H), 7.41 (Ar, 12H), 7.70 (Ar, 3H), 8.08 (Ar, 3H), 8.15 (Ar, 3H)
[0586] The compound S-8 (2.9 g) obtained above was dissolved in 15 mL of tetrahydrofuran (THF), and 40 mg of dibutyltin dilaurate was added. 510 mg of 2-isocyanatoethyl acrylate (produced by Showa Denko K.K., Karenz AOI) was added to the solution, and the reaction was carried out at room temperature. After 24 hours, 500 mg of 2-isocyanatoethyl acrylate was added, and the reaction was further carried out for 24 hours. After adding water to the reaction solution, 50 mL of ethyl acetate was added to extract the organic layer. The obtained organic layer was extracted twice with 30 mL of water, and the generated water layer was back-extracted twice with 50 mL of ethyl acetate. After drying the obtained organic layer with magnesium sulfate, it was concentrated below 30°C. The crude product obtained by the above concentration was purified using a silica gel column (hexane-ethyl acetate) to obtain compound M-5: 1.5 g (45% yield).
[0587] The NMR measurement data of compound M-5 are as follows.
[0588] 1HNMR (400MHz, CDCl3, δ, ppm) 2.53 (s, 6H), 3.07 (m, 2H), 3.53 (s, 2H), 3.99 (t, 2H), 4.14 (dd, 1H), 5.81 (d, 1H), 6.10 (dd, 1H), 6.40(d, 1H), 7.11(Ar, 12H), 7.24(Ar, 3H), 7.36(Ar, 3H), 7.43(Ar, 6H), 7.71(Ar, 3H), 8.08(Ar, 3H), 8.16(Ar, 3H)
[0589] A hologram recording medium 1 was prepared and evaluated in the same manner as in Example 1 except that the compound M-5 was used as the polymerizable monomer. The results are shown in Table 1 below.
[0590] (Example 6)
[0591] Compound M-6 was produced by the following synthesis method.
[0592] [Chemistry 23]
[0593]
[0594] The compound S-7 (2.0 g) obtained in Example 5, 2.7 g of thianthrene-1-boric acid, and 2.5 g of potassium carbonate were suspended in 20 mL of THF and 2.0 mL of water, and degassed by the circulation of nitrogen. 30 mg of dichlorobis[di-tert-butyl(p-dimethylaminophenyl)phosphino]palladium(II) was added to the reaction solution, and nitrogen was further passed for 10 minutes. The reaction solution was heated under a nitrogen atmosphere and stirred under reflux for 6 hours. After cooling to room temperature, it was extracted with ethyl acetate and washed with water. The aqueous layer was extracted twice with ethyl acetate, and 0.4 g of activated carbon was added to the obtained organic layer, and stirred for 30 minutes. After filtration with diatomaceous earth, it was concentrated, and the obtained crude product was purified using a silica gel column (hexane-ethyl acetate) to obtain compound S-9: 2.2 g (68% yield).
[0595] The NMR measurement data of compound S-9 are as follows.
[0596] 1 HNMR (400MHz, CDCl3, δ, ppm) 2.57 (m, 6H), 2.98 (d, 2H), 6.99 (Ar, 6H), 7.07 (Ar, 3H), 7.14 (Ar, 12H), 7.22 (Ar, 6H), 7.44 (Ar, 6H)
[0597] The compound S-9 (1.1 g) obtained above was dissolved in 7.5 mL of tetrahydrofuran (THF), and 10 mg of dibutyltin dilaurate was added. 290 mg of 2-isocyanatoethyl acrylate (produced by Showa Denko, Karenz AOI) was added to the solution, and the reaction was carried out at room temperature. After 24 hours, 300 mg of 2-isocyanatoethyl acrylate was added, and the reaction was further carried out for 24 hours. After adding water to the reaction solution, 50 mL of ethyl acetate was added to extract the organic layer. The obtained organic layer was extracted twice with 30 mL of water, and the generated water layer was back-extracted twice with 50 mL of ethyl acetate. The obtained organic layer was dried with magnesium sulfate and concentrated below 30°C. The crude product obtained by the above concentration was purified using a silica gel column (hexane-ethyl acetate) to obtain compound M-6: 600 mg (50% yield).
[0598] The NMR measurement data of compound M-6 are as follows.
[0599] 1 HNMR (400MHz, CDCl3, δ, ppm) 2.49 (m, 6H), 3.23 (m, 2H), 3.53 (s, 2H), 4.08 (t, 2H), 4 .52(dd, 1H), 5.82(d, 1H), 6.08(dd, 1H), 6.40(d, 1H), 7.10(Ar, 27H), 7.44(Ar, 6H)
[0600] A hologram recording medium 1 was prepared and evaluated in the same manner as in Example 1 except that the compound M-6 was used as the polymerizable monomer. The results are shown in Table 1 below.
[0601] (Example 7)
[0602] Compound M-7 was produced by the following synthesis method.
[0603] [Chemistry 24]
[0604]
[0605] Suspend 4.80 g of 3-bromobenzenethiol, 2.50 g of pentaerythritol tribromide, and 3.19 g of potassium carbonate in 13 mL of N,N-dimethylformamide (DMF). Heat the reaction mixture to 100°C and stir for 4 hours while confirming the progress of the reaction by LC analysis. After cooling to room temperature, extract with ethyl acetate and wash with water. Reverse extract the aqueous layer with ethyl acetate twice. Dry the obtained organic layer with Glauber's salt and concentrate it. The crude product obtained by the above concentration is purified by silica gel column (hexane-ethyl acetate) to obtain compound S-10: 5.0 g (100% yield).
[0606] The NMR measurement data of compound S-10 are as follows.
[0607] 1 HNMR (400MHz, CDCl3, δ, ppm) 3.15 (s, 6H), 3.66 (d, 2H), 7.09 (Ar, 3H), 7.25 (Ar, 6H), 7.45 (Ar, 3H)
[0608] The compound S-10 (2.3 g) obtained above, 3.2 g of dibenzothiophene-4-boric acid, and 2.9 g of potassium carbonate were suspended in 23 mL of THF and 3 mL of water, and degassed by the circulation of nitrogen. 70 mg of dichlorobis[di-tert-butyl(p-dimethylaminophenyl)phosphino]palladium(II) was added to the reaction solution, and nitrogen was further passed for 10 minutes. The reaction solution was heated under a nitrogen atmosphere and stirred under reflux for 6 hours. After cooling to room temperature, it was extracted with ethyl acetate and washed with water. The aqueous layer was extracted twice with ethyl acetate, and 0.5 g of activated carbon was added to the obtained organic layer, and stirred for 30 minutes. After filtration with diatomaceous earth, it was concentrated, and the obtained crude product was purified using a silica gel column (hexane-ethyl acetate) to obtain compound S-11: 2.9 g (87% yield).
[0609] The NMR measurement data of compound S-11 are as follows.
[0610] 1 HNMR (400MHz, CDCl3, δ, ppm) 3.37 (s, 6H), 3.82 (d, 2H), 7.28 (Ar, 3H), 7.34 (Ar, 3H), 7.41 (Ar, 15H), 7.71 (Ar, 6H), 8.05 (Ar, 3H), 8.11 (Ar, 3H)
[0611] The compound S-11 (2.9 g) obtained above was dissolved in 14.5 mL of tetrahydrofuran (THF), and 40 mg of dibutyltin dilaurate was added. 850 mg of 2-isocyanatoethyl acrylate (produced by Showa Denko, Karenz AOI) was added to the solution, and the reaction was carried out at room temperature. After 24 hours, 400 mg of 2-isocyanatoethyl acrylate was added, and the reaction was further carried out for 24 hours. After adding water to the reaction solution, 100 mL of ethyl acetate was added to extract the organic layer. The obtained organic layer was extracted twice with 50 mL of water, and the generated water layer was back-extracted twice with 50 mL of ethyl acetate. After drying the obtained organic layer with magnesium sulfate, it was concentrated below 30°C. The crude product obtained by the above concentration was purified using a silica gel column (hexane-ethyl acetate) to obtain compound M-7: 1.1 g (33% yield).
[0612] The NMR measurement data of compound M-7 are as follows.
[0613] 1 HNMR (400MHz, CDCl3, δ, ppm) 3.22 (m, 2H), 3.37 (s, 6H), 3.99 (t, 2H), 4.30 (s, 2H), 4.70 (dd, 1H), 5.62 (d, 1H), 5.82(dd, 1H), 6.23(d, 1H), 7.27(Ar, 3H), 7.38(Ar, 18H), 7.71(Ar, 6H), 8.05(Ar, 3H), 8.11(Ar, 3H)
[0614] A hologram recording medium 1 was prepared and evaluated in the same manner as in Example 1 except that the compound M-7 was used as the polymerizable monomer. The results are shown in Table 1 below.
[0615] (Example 8)
[0616] Compound M-8 was produced by the following synthesis method.
[0617] [Chemistry 25]
[0618]
[0619] The compound S-10 (1.0 g) obtained in Example 7, 1.6 g of thianthrene-1-boric acid, and 2.9 g of potassium phosphate were suspended in 14 mL of toluene, 7 mL of ethanol, and 7 mL of water, and degassed by the circulation of nitrogen. 30 mg of dichlorobis[di-tert-butyl(p-dimethylaminophenyl)phosphino]palladium(II) was added to the reaction solution, and nitrogen was further passed for 10 minutes. The reaction solution was heated under a nitrogen atmosphere and stirred under reflux for 6 hours. After cooling to room temperature, it was extracted with ethyl acetate and washed with water. The aqueous layer was extracted twice with ethyl acetate, and 0.5 g of activated carbon was added to the obtained organic layer, and stirred for 30 minutes. After filtration with diatomaceous earth, it was concentrated, and the obtained crude product was purified using a silica gel column (hexane-ethyl acetate) to obtain compound S-12: 1.6 g (98% yield).
[0620] The NMR measurement data of compound S-12 are as follows.
[0621] 1 HNMR (400MHz, CDCl3, δ, ppm) 3.27 (s, 6H), 3.73 (d, 2H), 7.01 (Ar, 9H), 7.09 (Ar, 6H), 7.19 (Ar, 6H), 7.31 (Ar, 6H), 7.38 (Ar, 6H)
[0622] The compound S-12 (1.6 g) obtained above was dissolved in 8.0 mL of tetrahydrofuran (THF), and 20 mg of dibutyltin dilaurate was added. 650 mg of 2-isocyanatoethyl acrylate (produced by Showa Denko K.K., Karenz AOI) was added to the solution, and the reaction was carried out at room temperature. After 24 hours, 650 mg of 2-isocyanatoethyl acrylate was added, and the reaction was further carried out for 24 hours. After adding water to the reaction solution, 60 mL of ethyl acetate was added to extract the organic layer. The obtained organic layer was extracted twice with 30 mL of water, and the generated water layer was back-extracted twice with 50 mL of ethyl acetate. The obtained organic layer was dried with magnesium sulfate and concentrated below 30°C. The crude product obtained by the above concentration was purified using a silica gel column (hexane-ethyl acetate) to obtain compound M-8: 1.0 g (54% yield).
[0623] The NMR measurement data of compound M-8 are as follows.
[0624] 1 HNMR (400MHz, CDCl3, δ, ppm) 3.23 (m, 2H), 3.35 (s, 6H), 4.00 (t, 2H), 4.29 (s, 2H), 4.89 (dd, 1H), 5 .68(d,1H),5.86(dd,1H),6.26(d,1H),7.07(Ar,9H),7.19(Ar,12H),7.34(Ar,6H),7.45(Ar,6H)
[0625] A hologram recording medium 1 was prepared and evaluated in the same manner as in Example 1 except that the compound M-8 was used as the polymerizable monomer. The results are shown in Table 1 below.
[0626] (Comparative Example 1)
[0627] Compound M-9 was produced by the following synthesis method.
[0628] [Chemistry 26]
[0629]
[0630] Dissolve 5 g of compound S-2 (DBTSH) obtained in the above synthesis example 1 and 2.7 g of potassium tert-butoxide in 50 mL of N,N-dimethylformamide (DMF). Add 2.25 g of pentaerythritol tribromide to the solution, raise the temperature to 80°C, and stir for 5 hours while confirming the reaction by LC analysis. The reaction solution was further cooled to 0°C, 1.3 mL of triethylamine and 0.68 mL of acryloyl chloride were added, the temperature was raised to 20°C, and stirred for 3 hours. After adding 50 mL of water to the reaction solution, 150 mL of ethyl acetate was added to extract the organic layer. The obtained organic layer was washed with 1 N hydrochloric acid and 1 N sodium hydroxide aqueous solution, and then concentrated. The crude product obtained by the above concentration was purified using a silica gel column (hexane-ethyl acetate) to obtain compound M-9: 2.3 g (43% yield).
[0631] The NMR measurement data of compound M-9 are as follows.
[0632] 1 HNMR (400MHz, CDCl3, δ, ppm) 3.41 (s, 6H), 4.23 (s, 2H), 5.46 (d, 1H), 5.67 (dd, 1H), 6.01 (d, 1H), 7.17 (Ar, 3H), 7.38 (Ar, 9H), 7.76 (Ar, 3H), 7.83 (Ar, 3H), 8.05 (Ar, 3H)
[0633] Hologram recording media 1 and 2 were prepared and evaluated in the same manner as in Example 1 except that compound M-9 was used as the polymerizable monomer. The results are shown in Table 1 below.
[0634] [Table 1]
[0635]
[0636] In the hologram recording medium 1, the molar concentrations of the polymerizable monomer, the photopolymerization initiator, and the additives in the polymerizable composition were kept constant, and only the type of the polymerizable monomer was changed.
[0637] In Comparative Example 1, totalΔn was 0.0123. In Examples 1, 2, 4 to 8, totalΔn was 0.0175, 0.0180, 0.0140, 0.0187, 0.0213, 0.0209, and 0.0211, respectively, which was increased by about 1.1 to 1.7 times compared with the case of Comparative Example 1.
[0638] As mentioned above, in the use of optical elements for AR glasses light guide plates, the higher the totalΔn, the brighter the projected image can be, and the wider the viewing angle can be. For example, when Δn = 1.7 times (0.0123 → 0.0213), the diffraction efficiency is equivalent to 2.1 times, which means that the brightness of the projected image is increased to 2.1 times. This means that, with the same projection image brightness, the power consumption is 0.5 times, or the battery life is extended to 2.1 times.
[0639] Furthermore, in memory applications, an increase in totalΔn can increase recording capacity.
[0640] Therefore, when the hologram recording medium is used for these purposes, it can be said that the compounds of the present invention used in Examples are superior to the compounds of Comparative Examples.
[0641] In hologram recording medium 2, compared with hologram recording medium 1, the compounding ratio of the polyol in the polymerizable composition was changed, and the molar concentrations of the polymerizable monomer, the photopolymerization initiator, and the additive were each doubled.
[0642] In Comparative Example 1 in which only the compound M-9 was used as the polymerizable monomer, total Δn was 0.0191.
[0643] On the other hand, in Example 1 using compound M-1, totalΔn was 0.0269; in Example 3 where compound M-3 and compound M-9 as polymerizable monomers were mixed in a molar ratio of 10:90, totalΔn was 0.0260, which was increased by about 1.4 times compared with the case of Comparative Example 1.
[0644] Therefore, it can be said that even if the mixing ratio of the polyol, the concentration of the polymerizable monomer, the photopolymerization initiator, and the radical scavenger are changed, the compound of the present invention is more suitable for use in a holographic recording medium than the compound of the comparative example.
[0645] [Refractive index]
[0646] The refractive index of the compound used as a monomer in Examples and Comparative Examples was measured by the following method.
[0647] The sample is dissolved in a mixed solution of 3-phenoxybenzyl acrylate and trimethylolpropane trimethacrylate in a mass ratio of 4:1 according to the specified concentration to prepare a test solution. The test solutions are of two types, 10% by mass and 20% by mass. The refractive index of each test solution is measured using a Kalnew precision refractometer (Shimadzu Corporation product name: KPR-2000). The temperature of the test solution is set to 23°C and the measurement wavelength is the helium lamp d line (587.6nm). Based on the measurement results, a calibration curve is prepared to show the correlation between the sample concentration and the refractive index. The refractive index when the sample concentration is 100% by mass is calculated based on the obtained calibration curve, and this is used as the refractive index of the sample.
[0648] [Table 2]
[0649] Compound Refractive Index Example 1 M-1 1.679 Example 2 M-2 1.685 Example 3 M-3 1.666 Example 5 M-5 1.692 Example 6 M-6 1.672 Example 7 M-7 1.691 Example 8 M-8 1.679 Comparative Example 1 M-9 1.720
[0650] [Refractive index estimated value]
[0651] The refractive index after curing was estimated for the compounds used as polymerizable monomers in Examples and Comparative Examples. The software used was Polymer-Design Tools Version 1.1 manufactured by DTW Associates, Inc. The refractive index value at 25° C. and 589 nm was estimated by the Bicerano method. The values are shown in Table 3 below.
[0652] The values equivalent to the above-mentioned measured values were obtained.
[0653] [Table 3]
[0654] Compound Estimated refractive index after curing Example 1 M-1 1.699 Example 2 M-2 1.676 Example 4 M-4 1.702 Comparative Example 1 M-9 1.719
[0655] The refractive index of the compound of the example is slightly lower than that of the compound of the comparative example, but as described above, the totalΔn of the holographic recording medium is a higher value. From this result, it can be seen that the polymerizability of the compound of the present invention is superior to that of the compound of the comparative example.
[0656] In the compound M-1 of the present invention, the tri(thiodibenzothiophene) group is bonded by a carbamate bond, and in the compound M-4 of the present invention, the tri(thiodibenzothiophene) group is bonded by an ester bond. It is believed that the acrylate group is not easily affected by steric hindrance due to the long spatial distance from the acrylate group, and has excellent polymerizability. In addition, it is believed that in compounds M-2, M-3, M-5 to M-8, the polymerizability is also excellent for the same reason.
[0657] On the other hand, in the comparative example compound M-9 in which the tris(thiodibenzothiophene) group was bonded via an ethyl group, it is considered that the acrylate group was easily affected by steric hindrance, and thus the polymerizability decreased.
[0658] Although the present invention has been described in detail using specific embodiments, it will be apparent to one skilled in the art that various modifications can be made without departing from the spirit and scope of the present invention.
[0659] This application is based on Japanese Patent Application No. 2019-208980 filed on November 19, 2019, the entire contents of which are incorporated herein by reference.
[0660] Explanation of symbols
[0661] S Holographic Recording Media
[0662] M1, M2, M3 reflectors
[0663] L1 Semiconductor laser source for recording light
[0664] L2 Regeneration laser source
[0665] PD1, PD2, PD3 Photodetectors
[0666] PBS Polarizing Beam Splitter
[0667] 1 LED unit
Claims
1. A compound represented by the following formula (1): [Chemistry 1] In formula (1), R 1 Represents a hydrogen atom or a methyl group; R 2 represents a dibenzothienyl group or a phenyl group having any one of a dibenzothienyl group, a benzothiazolyl group and a thianthrenyl group as a substituent; X 1 represents a urethane bond; L is a (m+1)-valent linking group and represents an unsubstituted hydrocarbon group having 1 to 8 carbon atoms; m represents 1 or 2; and n represents 0.
2. The compound according to claim 1, in, The above-mentioned L is an unsubstituted aliphatic hydrocarbon group having 1 to 8 carbon atoms.
3. The compound according to claim 2, in, The above-mentioned L is an unsubstituted chain aliphatic hydrocarbon group having 1 to 8 carbon atoms. 4 . A polymerizable composition comprising the compound according to claim 1 and a polymerization initiator. 5 . A holographic recording medium comprising the polymerizable composition according to claim 4 .
6. A polymer obtained by polymerizing the polymerizable composition according to claim 4.
7. An optical material comprising the polymer according to claim 6. An optical component comprising the polymer according to claim 6.
9. A large-capacity storage device comprising the holographic recording medium according to claim 5.
10. An optical element obtained by performing holographic recording on the holographic recording medium according to claim 5. AR glasses comprising the optical element according to claim 10.
Citation Information
Patent Citations
Titanocenes and radiation-curable composition containing same
JP1986151197A
Curable composition containing sulfonium compound and sensitizer
JP1993230189A
Photopolymerizable composition
JP1993241338A
Radiation-setting resin composition, resin composition for optical material and cured product therefrom
JP1994220131A
High-refractive-index resin composition excellent in scratch resistance
JP2000007741A
